Adhesive and adhesive sheet
By adjusting the ratio of refractive index and energy storage modulus in the adhesive, the problem of insufficient flexibility of existing high-refractive index adhesives is solved, and the high refractive index and flexibility is achieved, which is suitable for repeated bending operations. application.
Patent Information
- Application Number
- CN202380051520.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-18
AI Technical Summary
Existing high-refractive index adhesives have shortcomings in their softness and bonding properties, making it difficult to take into account both high refractive index and softness, especially in applications with repeated bending operations.
Develop a binder with a refractive index of 1.50 or more and the ratio of the energy storage modulus G' (25°C) and elongation EB at 25°C (G' (25°C)/EB) of the breaking modulus (G' (25°C)/EB) is above 1. And 50 or less, high refractive index and softness are achieved through this combination.
It achieves good flexibility and adhesive properties while having high refractive index, and is suitable for applications that need to withstand repeated bending operations.
Smart Images

Figure CN119487148A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive and an adhesive sheet. This application claims priority based on Japanese Patent Application No. 2022-110775 filed on July 8, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0002] Usually, adhesives (also called pressure-sensitive adhesives, the same below) are in a soft solid (viscoelastic) state within a temperature range near room temperature, and have the property of being easily adhered to an adherend by pressure. Taking advantage of such properties, adhesives are widely used for purposes such as joining, fixing, and protecting in various industrial fields ranging from home appliances to automobiles, various machinery, electrical equipment, and electronic equipment. As an example of the use of adhesives, the use of joining various light-transmitting components to each other or to other components in display devices such as liquid crystal display devices and organic EL display devices can be cited. As technical documents related to adhesives for optical components, Patent Document 1 and Patent Document 2 can be cited.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-169382
[0006] Patent Document 2: Japanese Patent Application Publication No. 2017-128732 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Patent documents 1 and 2 disclose an adhesive composition having a (meth)acrylate polymer as a main component containing a monomer having multiple aromatic rings as a monomer unit, and an adhesive formed by cross-linking the adhesive composition, and propose that the refractive index of the adhesive be made greater than 1.50, and particularly preferably greater than 1.51, by using a monomer having multiple aromatic rings. For example, among the materials for bonding adhesives to optical components, there are materials with high refractive indices, and it is known that when a conventional acrylic adhesive is used in the joining of such high refractive index materials, reflection occurs at the interface due to the difference in refractive indices between the two. By using an adhesive with a high refractive index as an adhesive for the joining of the above-mentioned high refractive materials, etc., the above-mentioned interface reflection can be prevented or suppressed. It should be noted that the refractive index of acrylic adhesives is generally about 1.47.
[0009] By the way, according to the application part and the use mode of the adhesive, an adhesive with good flexibility can be preferably used. For example, in recent years, as displays such as organic EL display devices used in electronic devices such as smart phones, foldable displays and rollable displays have been put into practical use, and the adhesive used in the above-mentioned purposes also needs to have the flexibility of the adherend that follows repeated bending. The adhesive with excellent flexibility is easy to follow and adhere to the surface of curved shapes such as three-dimensional shapes, and is suitable for electronic equipment with curved shapes. For an adhesive with a high refractive index, if the flexibility can be improved, it can also be applied to the above-mentioned purposes requiring flexibility, which is also useful. However, the high refractive index material used as the monomer component of the adhesive polymer has an aromatic ring, etc., and thus has a high tendency of glass transition temperature, and the adhesive formed using the high refractive index material has a tendency of insufficient flexibility (for example, the flexibility that can withstand repeated bending operations). In the design of the adhesive, there is a trade-off relationship between high refractive index and flexibility. If an adhesive that can balance both is realized, it is practically beneficial.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an adhesive having both a high refractive index and flexibility. Another object of the present invention is to provide an adhesive sheet including an adhesive layer containing the above adhesive.
[0011] Means used to solve problems
[0012] According to the present specification, the refractive index is 1.50 or more, and the storage modulus G'(25°C) [Pa] and the elongation at break E at 25°C are provided. B [%] Ratio (G'(25℃) / E B ) is 1 or more and 50 or less. According to the above adhesive, while having a high refractive index, the ratio (G'(25°C) / E B ) in the above range and can exert good flexibility. The adhesive is preferably used for bonding, fixing, protection, etc. in applications such as foldable displays where a high refractive index is desired and flexibility and tensile deformation that can withstand repeated bending operations are required.
[0013] In some embodiments, the elongation at break E B It is preferably 500% or more. With such an adhesive having such elongation, it is easy to obtain an adhesive satisfying the above ratio (G'(25°C) / E B ) has good softness.
[0014] In some embodiments, the storage modulus G' (25°C) is preferably 1.0×10 4 ~1.0×10 6According to the adhesive having such a low elastic modulus, it is easy to obtain the above ratio (G'(25℃) / E B ) has good softness.
[0015] In some embodiments, the glass transition temperature (Tg) of the adhesive is preferably 0°C or lower. With an adhesive having a Tg of 0°C or lower, it is easy to obtain a material that satisfies the above ratio (G'(25°C) / E B ) has good softness.
[0016] According to the present specification, an adhesive sheet comprising an adhesive layer is provided, wherein the adhesive layer comprises any adhesive disclosed herein (which may be an adhesive formed from any adhesive composition disclosed herein). The adhesive disclosed herein is formed into the form of an adhesive sheet, and is preferably used for bonding, fixing, protection, etc. in applications such as foldable displays that require a high refractive index and flexibility that can withstand repeated bending operations.
[0017] In some embodiments, the thickness of the adhesive layer is 5 μm or more and 100 μm or less. The technology disclosed herein can be preferably implemented in an embodiment with an adhesive layer having such a thickness.
[0018] In some embodiments, the haze of the adhesive sheet is 3% or less. Such a highly transparent adhesive sheet can be preferably used for applications requiring high light transmittance (eg, optical applications) and applications where the performance of an adherend can be well visually recognized through the adhesive sheet.
[0019] In some embodiments, the total light transmittance of the adhesive sheet is 85% or more. Such a highly transparent adhesive sheet can be preferably used for applications requiring high light transmittance (eg, optical applications) and applications where the adhesive sheet can be used to visually identify the properties of an adherend.
[0020] Some embodiments of the adhesive sheet have a peel strength of 0.1 N / 25 mm or more to a glass plate. The adhesive sheet having such an adhesive strength can be preferably used in a form of being attached to an adherend.
[0021] It should be noted that the technical solutions obtained by appropriately combining the elements described in this specification are also included in the scope of patent protection claimed by this patent application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.
[0023] Figure 2 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.
[0024] Figure 3This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment. DETAILED DESCRIPTION
[0025] The preferred embodiments of the present invention are described below. Matters necessary for implementing the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the art.
[0026] It should be noted that in the following drawings, the same reference numerals are sometimes used to describe components / parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, in order to clearly illustrate the present invention, the embodiments described in the drawings are schematic and do not necessarily accurately represent the size and scale of the actual product provided.
[0027] It should be noted that the "base polymer" of the adhesive refers to the main component of the rubbery polymer contained in the adhesive. The above-mentioned rubbery polymer refers to a polymer that exhibits rubber elasticity in a temperature range near room temperature. In addition, in this manual, the "main component" refers to a component with a content greater than 50% by weight unless otherwise specified.
[0028] <Adhesive Properties>
[0029] The adhesive disclosed herein is characterized in that the refractive index is 1.50 or more, and the storage modulus G'(25°C) [Pa] at 25°C and the elongation at break E B [%] Ratio (G'(25℃) / E B ) is greater than 1 and less than 50.
[0030] (Refractive Index)
[0031] The refractive index of the adhesive disclosed herein is not particularly limited as long as it is above 1.50, and can be set according to the purpose (for example, considering the refractive index of the adherend). According to the technology disclosed herein, an adhesive with the refractive index, an adhesive composition capable of forming the adhesive, and an adhesive sheet comprising the above-mentioned adhesive can be provided. In some embodiments, the refractive index of the above-mentioned adhesive can be, for example, above 1.510, above 1.520, above 1.530, above 1.540, above 1.550 or above 1.560 (for example, greater than 1.570). In some preferred embodiments, the refractive index of the above-mentioned adhesive can be above 1.575, above 1.580, above 1.585, above 1.590, and above 1.595. According to the adhesive with the refractive index, in the use method of sticking to the material with high refractive index, the light reflection at the interface with the adherend can be appropriately suppressed. The preferred upper limit of the refractive index of the adhesive may vary depending on the refractive index of the adherend, etc., and is therefore not limited to a specific range, and may be, for example, below 1.700, below 1.670, below 1.650, below 1.620, or below 1.600. In some embodiments that place more emphasis on flexibility and low temperature properties, the refractive index of the adhesive may be, for example, less than 1.595, less than 1.590, less than 1.580, less than 1.570, less than 1.560, less than 1.550, or less than 1.540. The refractive index of the adhesive may be adjusted, for example, by the composition of the adhesive. For example, the type of base polymer, the composition ratio of the monomer components, additives (such as additives (H RO ), preferably the presence or absence of additives (A), type and amount of use, etc. are adjusted.
[0032] It should be noted that, in this specification, the refractive index of the adhesive refers to the refractive index of the surface (adhesive surface) of the adhesive. The refractive index of the adhesive can be measured using a prism coupler at a measurement temperature of 25°C and a measurement wavelength of 594nm. As a prism coupler, a commercially available measuring device can be used, for example, the model "2010M" manufactured by Metricon or its equivalent. As a measurement sample, an adhesive layer containing the adhesive to be evaluated can be used. The refractive index of the adhesive can be specifically measured by the method described in the embodiments described later.
[0033] (Ratio (G'(25℃) / E B ))
[0034] The ratio of the adhesive disclosed herein (G'(25°C) / E B ) is 1 or more and 50 or less. That is, the following formula is satisfied: 1≤(G'(25°C) / E B)≤50. The above ratio (G'(25℃) / E B ) is composed of the numerical portion of the storage modulus G'(25°C) of the adhesive at 25°C expressed in "Pa" and the elongation at break E of the adhesive expressed in "%" B Storage modulus G'(25℃) is higher (harder), and elongation at break E B The smaller the ratio (G'(25℃) / E B ) is larger. For example, brittle materials or weak (low cohesive) materials are easily torn apart due to elongation deformation, and have a breaking elongation E B On the other hand, the storage modulus G' (25°C) is further reduced, and the elongation at break E is further increased. B The above ratio (G'(25℃) / E B ) has an effect in the direction of further reducing the ratio. B ) in the range of 1 to 50, the adhesive exhibits good flexibility due to moderate flexibility and moderate elongation and deformation (non-breakability). B ) in the above range, can take into account both high refractive index and softness. Adhesives with the above softness can also be used for applications where repeated bending is envisioned.
[0035] From the viewpoint of achieving better flexibility, in some embodiments, the ratio (G'(25°C) / E B ) is preferably 40 or less (e.g., 35 or less), more preferably 30 or less, and may be 25 or less, 20 or less, 15 or less, or 10 or less. In addition, in consideration of the balance with other properties (e.g., optical properties, high temperature properties, low temperature properties, etc.), in some embodiments, the ratio (G'(25°C) / E B ) can be 2 or more, 3 or more, 5 or more, 10 or more, 15 or more, or 20 or more.
[0036] (Elongation at break E B )
[0037] The elongation at break E of the adhesive disclosed herein is B There is no particular limitation, and the desired ratio (G'(25°C) / E B ) is appropriately set within the range of . The elongation at break E of the adhesive B For example, it can be in the range of 200% or more and 10000% or less. In some embodiments, the elongation at break E BFor example, it can be 300% or more, preferably 400% or more, preferably 500% or more, more preferably 750% or more, and further preferably 1000% or more. In some embodiments that place more emphasis on elongation and deformability, the elongation at break E of the adhesive is B Preferably, it is 1250% or more, more preferably 1500% or more, may be 1750% or more, may be 2000% or more, may be 2250% or more, 2500% or more, 3000% or more, 4000% or more or 5000% or more. In addition, from the viewpoint of the processability and handling of the adhesive or the adhesive sheet having the adhesive, in some embodiments, the elongation at break E of the adhesive is B It is preferably 9000% or less, 8000% or less is advantageous, 7000% or less is preferred, 6000% or less is more preferred, it can be 5500% or less, it can be 5000% or less, it can be 4500% or less, it can be 4000% or less, it can be 3500% or less.
[0038] Elongation at break of adhesive B The elongation at break E of the adhesive can be measured by the method described in the examples below. B For example, it can be adjusted by selecting the composition of the monomer components constituting the base polymer, selecting the type and amount of additives, and selecting the presence or absence of a crosslinking agent and the type and amount of crosslinking agent.
[0039] (Storage modulus G')
[0040] The storage modulus G'(25°C) at 25°C of the adhesive disclosed herein is not particularly limited, and can be adjusted to achieve a desired ratio (G'(25°C) / E B The storage modulus G' (25°C) can be set appropriately within the range of 1.0×10 6 Pa or less, can be 5.0×10 5 Pa or less. The adhesive having the above storage modulus G'(25°C) has moderate flexibility in the temperature range from near room temperature to above room temperature, for example, it can be well adhered to the adherend. It is easy to achieve both a high refractive index and a ratio (G'(25°C) / E B ) from the perspective of the adhesive, in some embodiments, the storage modulus G' (25°C) is less than 2.0×10 5 Pa is favorable and preferably less than 1.5×10 5 Pa, more preferably less than 1.2×10 5 Pa, can be less than 1.0×10 5 Pa, can be less than 9.0×10 4 , can be less than 8.0×10 4Pa, can be less than 7.0×10 4 Pa, can be less than 6.5×10 4 Pa, can be less than 6.0×10 4 Pa, can be less than 5.0×10 4 Pa, less than 4.0×10 4 Pa or less than 3.0×10 4 Pa.
[0041] The lower limit of the storage modulus G' (25°C) is not particularly limited, and can be, for example, 1.0×10 3 Pa or more, can be 5.0×10 3 Pa or above, it can be 6.0×10 3 Pa or more, it can be 8.0×10 3 Pa or more, can be 1.0×10 4 Pa, it can be 1.2×10 4 Pa or above, it can be 1.5×10 4 Pa, it can be 1.6×10 4 Pa or more (for example, greater than 1.6×10 4 Pa), or 1.7×10 4 Pa or more. When the storage modulus G'(25°C) is greater than the specified value, the adhesive can easily have moderate cohesion from, for example, near room temperature to a high temperature region. An adhesive having moderate cohesion near room temperature (for example, 25°C) can easily achieve both a high refractive index and a ratio (G'(25°C) / E B ), and thus is preferred. In some embodiments, the storage modulus G' (25°C) of the adhesive may be 2.0×10 4 Pa or above, it can be 2.5×10 4 Pa or above, it can be 3.5×10 4 Pa or more, it can be 4.0×10 4 Pa or above.
[0042] The storage modulus G'(60°C) at 60°C of the adhesive disclosed herein is not particularly limited, and is, for example, less than 1.0×10 6 Pa is appropriate, preferably less than 5.0×10 5 Pa, more preferably less than 2.0×10 5 Pa, can be less than 1.5×10 5 Pa, can be less than 1.0×10 5 Pa, can also be less than 0.8×10 4Pa. As described above, the adhesive having a limited storage modulus G'(60°C) has good flexibility in a high temperature region. The lower limit of the storage modulus G'(60°C) is not particularly limited, and is, for example, 5.0×10 2 Pa or above, 1.0×10 3 Pa or more is appropriate, and preferably 2.0×10 3 Pa or more, more preferably 3.0×10 3 Pa or more, can be 5.0×10 3 Pa or more. A binder having the above storage elastic modulus G' (60°C) has a moderate cohesive force even in a high temperature range and tends to have excellent heat resistance, and is therefore preferred.
[0043] The storage modulus G'(-20°C) of the adhesive disclosed herein at -20°C is not particularly limited, and can be, for example, less than 1.0×10 9 Pa, less than 2.0×10 8 Pa is appropriate and can be 1.5×10 8 Pa or less, can be 1.0×10 8 Pa or less, can be 5.0×10 7 Pa or less, can be 1.0×10 7 Pa or less, can be 5.0×10 6 Pa or less, can be 4.0×10 6 Pa or less, can be 3.0×10 6 Pa or less. As described above, the adhesive having a limited storage modulus G'(-20°C) can have particularly excellent flexibility. For example, it can have good flexibility in a lower temperature range and have flexibility that can withstand repeated bending operations in a wide temperature range including a low temperature range. The lower limit of the storage modulus G'(-20°C) is not particularly limited, for example, 5.0×10 3 Pa or more is appropriate, and preferably 1.0×10 4 Pa or more, more preferably 5.0×10 4 Pa or more, can be 1.0×10 5 Pa or more, can be 5.0×10 5 Pa or more, can be 1.0×10 6 Pa or more. The adhesive having the above storage elastic modulus G'(-20°C) can have both flexibility and moderate cohesive force. In addition, the adhesive having the above storage elastic modulus G'(-20°C) tends to easily achieve both high refractive index and flexibility in a low temperature range.
[0044] (Storage modulus ratio)
[0045] In some embodiments, as an adhesive, an adhesive having a ratio of the storage modulus G'(25°C) at 25°C to the storage modulus G'(60°C) at 60°C (G'(25°C) / G'(60°C)) in the range of 1 to 30 is used. According to the adhesive satisfying the above characteristics, the change in elastic modulus in the temperature range from room temperature to the high temperature range is suppressed, so it is easy to exhibit stable characteristics (flexibility, etc.) with respect to temperature changes. It is appropriate for the above ratio (G'(25°C) / G'(60°C)) to be 10 or less, it is advantageous to be 5.0 or less, it is preferably 4.0 or less (for example, 3.0 or less), it is more preferably 2.5 or less, it can be 2.0 or less, and it can be 1.8 or less. The lower limit value of the above ratio (G'(25°C) / G'(60°C)) can be, for example, greater than 1.1. Taking into account the balance with other characteristics, in some embodiments, the ratio (G'(25°C) / G'(60°C)) may be 1.2 or more, 1.3 or more, 1.4 or more, or 1.5 or more.
[0046] In some embodiments, as an adhesive, an adhesive having a ratio of the storage modulus G'(-20°C) at -20°C to the storage modulus G'(25°C) at 25°C (G'(-20°C) / G'(25°C)) in the range of 1 to 1000 is used. According to the adhesive satisfying the above characteristics, the change in elastic modulus in the temperature range from the low temperature range to the room temperature range is suppressed, so it is easy to exhibit stable characteristics (flexibility, etc.) with respect to temperature changes, which is preferred. It is appropriate for the above ratio (G'(-20°C) / G'(25°C)) to be 900 or less, preferably 750 or less, more preferably 600 or less, may be 500 or less, may be 300 or less, may be 200 or less, may be 100 or less, or may be 80 or less. The lower limit value of the above ratio (G'(-20°C) / G'(25°C)) can be, for example, greater than 1.5. Taking into account the balance with other characteristics, the lower limit value of the above ratio (G'(-20°C) / G'(25°C)) can be greater than 5.0, greater than 10, greater than 15 or greater than 20.
[0047] In some embodiments, as an adhesive, an adhesive having a ratio of the storage modulus G'(-20°C) at -20°C to the storage modulus G'(60°C) at 60°C (G'(-20°C) / G'(60°C)) in the range of 1 to 3000 is used. According to the adhesive satisfying the above characteristics, the change in elastic modulus is suppressed in a wide temperature range from a lower temperature range to a high temperature range, so that stable characteristics (flexibility, etc.) can be exhibited against temperature changes. It is advantageous for the above ratio (G'(-20°C) / G'(60°C)) to be 2500 or less, preferably 2000 or less, and may be 1500 or less, 1200 or less, 800 or less, 600 or less, 400 or less, 300 or less, 200 or less, or 100 or less. The lower limit of the ratio (G'(-20°C) / G'(60°C)) may be, for example, 2.0 or more, or 5.0 or more, 10 or more, or 20 or more in consideration of the balance with other characteristics.
[0048] (Glass transition temperature)
[0049] The glass transition temperature (Tg) of the adhesive is not particularly limited, and can be set in consideration of the flexibility in the temperature range near room temperature, the elongation deformation, the flexibility in the low temperature range, and the cohesion (heat resistance, etc.) in the high temperature range. In some embodiments, the Tg of the adhesive can be, for example, below 30°C, below 20°C, below 10°C, or below 5°C. In some preferred embodiments, from the viewpoint of flexibility and tensile deformation, it is appropriate that the Tg of the adhesive is below 0°C, more preferably below -5°C, further preferably below -10°C, and can be below -15°C (for example, below -20°C). The lower the Tg of the adhesive, the better the adhesive properties such as adhesion to the adherend. In addition, by setting the Tg of the adhesive to a lower level, the change in the elastic modulus in the temperature range higher than the Tg can be suppressed. The lower limit of the Tg of the adhesive is, for example, above -50°C, preferably above -40°C, and can be above -30°C. According to the adhesive having the above Tg, there is a tendency to easily obtain moderate cohesion. In addition, there is a tendency to easily form an adhesive having both a high refractive index and flexibility.
[0050] The storage modulus G' of the adhesive at each temperature and the glass transition temperature Tg of the adhesive can be measured by the method described in the examples described later, and the storage modulus ratios can be calculated based on the results. The storage modulus G', storage modulus ratios and glass transition temperature Tg of the adhesive can be adjusted by, for example, selecting the composition of the monomer components constituting the base polymer, the type and amount of additives, the presence or absence of the use of a cross-linking agent, the type and amount of cross-linking agent, etc.
[0051] <Composition of Adhesive>
[0052] The adhesive disclosed herein can be formed using an adhesive composition containing components (adhesive forming components) corresponding to the composition of the adhesive. The adhesive can be an adhesive formed by curing an adhesive composition in the form of a solvent-type, active energy ray-curable, water-dispersible, hot-melt type, etc. by drying, cross-linking, polymerization, cooling, etc., i.e., a cured product of the above-mentioned adhesive composition. The curing method of the adhesive composition (e.g., drying, cross-linking, polymerization, cooling, etc.) can be applied only one, and two or more can be applied simultaneously or in multiple stages. For a solvent-based adhesive composition, an adhesive can typically be formed by drying the composition (preferably further cross-linking). For an active energy ray-curable adhesive composition, an adhesive can be formed by typically irradiating active energy rays to cause a polymerization reaction and / or a cross-linking reaction. In the case where it is necessary to dry the active energy ray-curable adhesive composition, active energy rays can be irradiated after drying. From the viewpoints of the ease of preparation of the adhesive composition, the adhesive disclosed herein can be preferably formed using a solvent-based adhesive composition.
[0053] The type of the above-mentioned adhesive is not particularly limited, for example, it can be an acrylic adhesive, a rubber adhesive (natural rubber, synthetic rubber, their mixed type, etc.), a polysiloxane adhesive, a polyester adhesive, a urethane adhesive, a polyether adhesive, a polyamide adhesive, a fluorine-containing adhesive, etc. The above-mentioned acrylic adhesive refers to an adhesive using an acrylic polymer as a base polymer. It is also the same for other adhesives such as rubber. From the viewpoints of the ease of adjustment of the adhesive properties, optical properties, etc., acrylic adhesives are preferred in some ways.
[0054] In this specification, "acrylic polymer" refers to a polymer containing a monomer unit derived from a monomer having at least one (meth)acryloyl group in one molecule as a monomer unit constituting the polymer. Hereinafter, a monomer having at least one (meth)acryloyl group in one molecule is also referred to as an "acrylic monomer". Therefore, the acrylic polymer in this specification is defined as a polymer containing a monomer unit derived from an acrylic monomer. As a typical example of an acrylic polymer, an acrylic polymer in which more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of the monomer components constituting the polymer are acrylic monomers can be cited.
[0055] In addition, in this specification, "acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, "(meth)acryloyl" collectively means acryloyl and methacryloyl. Therefore, the concept of acrylic monomer mentioned here can include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). Similarly, in this specification, "(meth)acrylic acid" collectively means acrylic acid and methacrylic acid, and "(meth)acrylate" collectively means acrylate and methacrylate. The same is true for other similar terms.
[0056] In addition, in this specification, the so-called "monomer component constituting the polymer", whether it is contained in the adhesive composition in the form of a preformed polymer (which may be an oligomer) or in the form of an unpolymerized monomer, refers to the monomer constituting the repeating unit (monomer unit) of the polymer in the adhesive formed by the adhesive composition. That is, the monomer component constituting the specified polymer (e.g., a base polymer, preferably an acrylic polymer) contained in the adhesive can be contained in the above-mentioned adhesive composition in any form of a polymer, an unpolymerized polymer, or a partial polymer. From the viewpoint of the ease of preparation of the adhesive composition, in some embodiments, it is preferred to include substantially all (e.g., more than 95% by weight, preferably more than 99% by weight) of the monomer component in the form of a polymer.
[0057] Hereinafter, a pressure-sensitive adhesive containing an acrylic polymer as a base polymer (acrylic pressure-sensitive adhesive) will be mainly described, but the pressure-sensitive adhesive in the technology disclosed herein is not intended to be limited to the acrylic pressure-sensitive adhesive.
[0058] (monomer (m1))
[0059] In some embodiments, the acrylic polymer preferably contains a (meth)acrylic acid alkyl ester having a chain alkyl group at the ester terminal (hereinafter also referred to as "monomer (m1)") as a monomer component constituting the acrylic polymer. The chain alkyl group in the monomer (m1) may be linear or branched. Monomers (m1) may be used alone or in combination of two or more.
[0060] As the monomer (m1), for example, a compound represented by the following formula (1) can be preferably used.
[0061] CH2=C(R 1 )COOR 2 (1)
[0062] Among them, R in the above formula (1) 1 is a hydrogen atom or a methyl group, R 2The carbon number of the chain alkyl group is, for example, 1 to 20, preferably 1 to 18. The (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the chain alkyl group, i.e., (meth)acrylic acid C 1-20 Specific examples of the alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and nonyl (meth)acrylate. , isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc., but are not limited to these substances.
[0063] In the mode that the monomer component constituting the acrylic polymer contains monomer (m1), the content of the (meth) alkyl acrylate in the monomer component can be set in a mode that appropriately exerts its use effect. The content of the (meth) alkyl acrylate in the monomer component can be, for example, 1% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more. From the viewpoint of easily taking into account high refractive index and flexibility in a balanced manner, in some modes, the content of the (meth) alkyl acrylate in the monomer component is appropriate to be 40% by weight or more, advantageous to be 45% by weight or more, preferably 50% by weight or more (for example, greater than 50% by weight), 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, or 90% by weight or more, 95% by weight or more, or 100% by weight. In addition, from the viewpoint of easily obtaining an adhesive having moderate cohesiveness, in some embodiments, the content of the alkyl (meth)acrylate in the monomer component is appropriately 99.9% by weight or less, preferably 99.8% by weight or less, more preferably 99.6% by weight or less, and may be 99.5% by weight or less, 99.0% by weight or less, 95% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, 75% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less.
[0064] In some embodiments, as at least a part of the monomer (m1), an alkyl (meth)acrylate having a homopolymer Tg of less than -20°C (more preferably less than -40°C, for example less than -50°C) can be preferably used. Such a low-Tg alkyl (meth)acrylate can contribute to the low elastic modulus of the adhesive. In addition, it can also contribute to the improvement of adhesive properties such as adhesive strength. The lower limit of the Tg of the above-mentioned alkyl (meth)acrylate is not particularly limited, for example, it can be above -85°C, above -75°C, above -65°C, or above -60°C. Specific examples of the above-mentioned low-Tg alkyl (meth)acrylates include n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), heptyl acrylate, octyl acrylate, isononyl acrylate (iNA), etc.
[0065] In other embodiments, as at least a part of the monomer (m1), an alkyl (meth)acrylate having a homopolymer Tg greater than -20°C (e.g., above -10°C) may be used. The upper limit of the Tg of the above-mentioned alkyl (meth)acrylate is, for example, below 10°C, below 5°C, or below 0°C. Alkyl (meth)acrylates having a Tg in this range (hereinafter also referred to as "medium Tg") can help adjust the elastic modulus of the adhesive. Although not particularly limited, the alkyl (meth)acrylate having the above-mentioned Tg (medium Tg) is preferably used in combination with the above-mentioned low Tg alkyl (meth)acrylate. As a specific example of a medium Tg alkyl (meth)acrylate, lauryl acrylate (LA) can be cited. Alternatively, the technology disclosed herein may also be implemented in a manner that substantially does not use a medium Tg alkyl (meth)acrylate.
[0066] In some embodiments of using the monomer (m1), as the monomer (m1), (meth)acrylic acid C is preferably used. 4-8 Among them, acrylic acid C is more preferably used. 4-8 Alkyl ester. (Meth) acrylic acid C 4-8 The alkyl esters may be used alone or in combination of two or more. 4-8 Alkyl esters tend to reduce the elastic modulus of the adhesive and to provide good adhesive properties (adhesive strength, etc.). 4-8 In the embodiment in which the alkyl ester is used as the monomer (m1), the (meth)acrylic acid C in the monomer (m1) 4-8 The proportion of the alkyl ester is appropriately 30% by weight or more, preferably 50% by weight or more, more preferably 70% by weight or more, further preferably 90% by weight or more, and may be substantially 100% by weight.
[0067] In some embodiments of using the monomer (m1), the (meth)acrylic acid C in the monomer component 4-8 The content of the alkyl ester may be, for example, 1% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more, or 40% by weight or more, 45% by weight or more, 50% by weight or more, more than 50% by weight, 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more, or 100% by weight. In some embodiments, the (meth)acrylic acid C in the monomer component may be 1% by weight or more. 4-8The content of the alkyl ester may be, for example, 99.9% by weight or less, 99.8% by weight or less, 99.6% by weight or less, 99.5% by weight or less, 99.0% by weight or less, 95% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less, or 70% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less.
[0068] In some embodiments of using the monomer (m1), as the monomer (m1), (meth)acrylic acid C 1-6 Alkyl esters. By using (meth) acrylic acid C 1-6 Alkyl esters can adjust the storage modulus in each temperature range. For example, the storage modulus in the high temperature range can be set relatively high. (Meth) acrylic acid C 1-6 The alkyl ester can contribute to the improvement of transparency (for example, the reduction of haze). 1-6 The alkyl acrylate tends to have excellent copolymerizability with the monomer (m3) described later. (Meth)acrylic acid C 1-6 The alkyl ester may be used alone or in combination of two or more. 1-6 Alkyl ester, preferably acrylic acid C 1-6 Alkyl ester, more preferably acrylic acid C 2-6 Alkyl ester, more preferably acrylic acid C 4-6 In some other embodiments, (meth)acrylic acid C 1-6 The alkyl ester is preferably (meth)acrylic acid C 1-4 Alkyl ester, more preferably (meth) acrylic acid C 2-4 Alkyl ester, more preferably acrylic acid C 2-4 Alkyl esters. As (meth) acrylic acid C 1-6 A preferred example of the alkyl ester is BA.
[0069] (Meth)acrylic acid C in the monomer components constituting the acrylic polymer 1-6 The content of the alkyl ester may be, for example, 1% by weight or more, 3% by weight or more, 5% by weight or more, or 8% by weight or more. From the perspective of low elastic modulus, transparency, etc., in some embodiments, the (meth) acrylic acid C 1-6The content of the alkyl ester may be, for example, 10% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more, or 40% by weight or more, 45% by weight or more, 50% by weight or more, more than 50% by weight, 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more, or 100% by weight. In some embodiments, the (meth)acrylic acid C in the monomer component may be 100% by weight. 1-6 The content of the alkyl ester may be, for example, 99.9% by weight or less, 99.8% by weight or less, 99.6% by weight or less, 99.5% by weight or less, 99.0% by weight or less, 95% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less, and may be 70% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less. From the viewpoint of better exerting the effects of other monomers, the (meth)acrylic acid C in the monomer component may be less than 1% by weight. 1-6 The content of the alkyl ester may be 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, 10% by weight or less, or 5% by weight or less, or may be less than 3% by weight or less than 1% by weight. The technology disclosed herein may also be used without substantially using (meth) acrylic acid C 1~6 The method is implemented as an alkyl ester.
[0070] In another embodiment of using the monomer (m1), as the monomer (m1), (meth)acrylic acid C 7-12 By using (meth) acrylic acid C 7-12 Alkyl esters can satisfactorily reduce the storage modulus. (Meth) acrylic acid C 7-12 Alkyl esters can also help improve adhesion (peel strength). (Meth) acrylic acid C 7-12 The alkyl ester may be used alone or in combination of two or more. 7-12 Alkyl ester, preferably acrylic acid C 7-10 Alkyl ester, more preferably acrylic acid C 7-9 Alkyl ester, more preferably C8 alkyl acrylate. 7-12 Examples of the alkyl ester include 2EHA, iNA, and LA, and a preferred example is 2EHA.
[0071] (Meth)acrylic acid C in the monomer components constituting the acrylic polymer 7-12The content of the alkyl ester may be, for example, 1% by weight or more, 3% by weight or more, 5% by weight or more, or 8% by weight or more. From the perspective of low elastic modulus, transparency, adhesiveness, etc., in some embodiments, the (meth) acrylic acid C 7-12 The content of the alkyl ester may be, for example, 10% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more, or 40% by weight or more, 45% by weight or more, 50% by weight or more, more than 50% by weight, 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more, or 100% by weight. In some embodiments, the (meth)acrylic acid C in the monomer component may be 100% by weight. 7-12 The content of the alkyl ester may be, for example, 99.9% by weight or less, 99.8% by weight or less, 99.6% by weight or less, 99.5% by weight or less, 99.0% by weight or less, 95% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, or 75% by weight or less, and may be 70% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less. From the perspective of better exerting the effects of other monomers, the content may be 50% by weight or less, 40% by weight or less, 30% by weight or less, 20% by weight or less, 10% by weight or less, or 5% by weight or less, and may be less than 3% by weight or less than 1% by weight. The technology disclosed herein can be used without substantially using (meth) acrylic acid C 7-12 The method is implemented as an alkyl ester.
[0072] In some embodiments in which the monomer component includes monomer (m1), from the viewpoint of low elastic modulus, at least a portion of the above-mentioned monomer (m1) is preferably an alkyl acrylate. The use of alkyl acrylate is also advantageous from the viewpoint of adhesive properties such as adhesive strength. For example, 50% by weight or more of the monomer (m1) is preferably an alkyl acrylate, and the proportion of the alkyl acrylate in the monomer (m1) is more preferably 75% by weight or more, and further preferably 90% by weight or more, and substantially 100% by weight of the monomer (m1) may be an alkyl acrylate. It may be a mode in which only one or more alkyl acrylates are used as monomer (m1) without using alkyl methacrylates.
[0073] (monomer(m2))
[0074] In some preferred embodiments, the monomer components constituting the acrylic polymer may contain a monomer (m2). The above-mentioned monomer (m2) is a monomer belonging to at least one of a monomer having a hydroxyl group (hydroxyl-containing monomer) and a monomer having a carboxyl group (carboxyl-containing monomer). The above-mentioned hydroxyl-containing monomer is a compound having at least one hydroxyl group and at least one ethylenically unsaturated group in one molecule. The above-mentioned carboxyl-containing monomer is a compound containing at least one carboxyl group and at least one ethylenically unsaturated group in one molecule. Monomer (m2) can help introduce crosslinking points into the acrylic polymer or impart moderate cohesion to the adhesive. Monomer (m2) can be used alone or in combination of two or more. Monomer (m2) is typically a monomer that does not contain an aromatic ring.
[0075] Examples of ethylenically unsaturated groups possessed by the monomer (m2) include (meth)acryloyl, vinyl, (meth)allyl, etc. From the viewpoint of polymerization reactivity, (meth)acryloyl is preferred, and from the viewpoint of low elastic modulus and adhesion, acryloyl is more preferred. From the viewpoint of low elastic modulus of the adhesive, as the monomer (m2), a compound having 1 ethylenically unsaturated group contained in one molecule (i.e., a monofunctional monomer) is preferably used.
[0076] In some embodiments, as monomer (m2), a monomer having a relatively long distance between an ethylenically unsaturated group (e.g., (meth) acryloyl) and a hydroxyl group and / or a carboxyl group can be used. Thus, in the manner in which the above-mentioned hydroxyl group and / or carboxyl group are used for cross-linking reaction, a cross-linked structure with high flexibility can be easily obtained. For example, a compound having a number of more than 3 (e.g., more than 4, more than 5, more than 6, more than 7, more than 8, more than 9, more than 10, more than 11, more than 12, more than 13, more than 14, more than 15, more than 16, more than 17, more than 18, or more than 19) of atoms (typically carbon atoms, oxygen atoms) constituting the chain (connection chain) connecting the above-mentioned ethylenically unsaturated group and the hydroxyl group and / or carboxyl group can be used as a monomer (m2). The upper limit of the number of atoms constituting the above-mentioned connection chain is, for example, less than 45, and can be less than 20 (e.g., less than 19, less than 18, less than 17, less than 16, less than 15, less than 14, less than 13, less than 12, less than 11, less than 10, less than 9, or less than 8). It should be noted that the number of atoms constituting the connecting chain connecting the above ethylenically unsaturated group and the hydroxyl group and / or the carboxyl group refers to the minimum number of atoms required to reach the hydroxyl group or the carboxyl group from the ethylenically unsaturated group. n -yl), the number of n is the number of atoms constituting the above-mentioned connecting chain. In addition, for example, when the above-mentioned connecting chain is oxyethylene (i.e., -(C2H4O) n-(CH2)-, the product of 3 (3n) of the sum of the carbon atoms 2 and the oxygen atoms 1 constituting the oxyethylene group and n is the number of atoms constituting the above-mentioned connecting chain. Although not particularly limited, as such a monomer (m2), a monomer having a -(CH2)- n -, an alkylene unit represented by -(C m H 2m The monomer (m2) is a monomer containing at least one of the oxyalkylene units represented by (for example, an oxyethylene unit in which m is 2 in the above formula, an oxypropylene unit in which m is 3 in the above formula, and an oxybutylene unit in which m is 4 in the above formula). The number of the above alkylene units and oxyalkylene units is not particularly limited, and may be 1 or more (for example, 1 to 15 or 1 to 10 or 2 to 6 or 2 to 4). In addition, n in the formula representing the above alkylene unit is, for example, an integer of 1 to 10, may be 2 or more, may be 3 or more, may be 4 or more, and may be 6 or less, or may be 5 or less. m in the formula representing the above oxyalkylene unit is an integer of 2 or more, for example, an integer of 2 to 4. The monomer (m2) may be a monomer containing an ester bond, an ether bond, a thioether bond, an aromatic ring, an aliphatic ring, a heterocyclic ring (for example, a ring containing a nitrogen atom (N), an oxygen atom (O), or a sulfur atom (S)) in addition to the above ethylenically unsaturated group, hydroxyl group and / or carboxyl group, alkylene unit and / or oxyalkylene unit. Furthermore, the above-mentioned alkylene unit and oxyalkylene unit may have a substituent.
[0077] Examples of hydroxyl-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, but are not limited to these. Examples of hydroxyl-containing monomers that can be preferably used include 4-hydroxybutyl acrylate (Tg: -40°C) and 2-hydroxyethyl acrylate (Tg: -15°C). From the viewpoint of improving flexibility in the room temperature region, 4-hydroxybutyl acrylate having a lower Tg is more preferred. In addition, in the method of using a hydroxyalkyl (meth)acrylate as a hydroxyl-containing monomer and using the hydroxyl group in a cross-linking reaction, from the viewpoint of obtaining a cross-linked structure with high flexibility, it is preferred to use a monomer having a large number of carbon atoms in the hydroxyalkyl group of the above-mentioned hydroxyalkyl (meth)acrylate, for example, a hydroxyalkyl (meth)acrylate having a carbon number of 3 or more (for example, 3 to 12, preferably 4 to 10) (for example, 4-hydroxybutyl acrylate). In a preferred embodiment, 50% by weight or more (for example, greater than 50% by weight, greater than 70% by weight, or greater than 85% by weight) of the monomer (m2) may be 4-hydroxybutyl acrylate. The hydroxyl-containing monomer may be used alone or in combination of two or more.
[0078] In some embodiments of using a hydroxyl-containing monomer as a monomer (m2), the hydroxyl-containing monomer may be one or more selected from compounds that do not have a methacryloyl group. As preferred examples of hydroxyl-containing monomers that do not have a methacryloyl group, the various hydroxyalkyl acrylates described above may be cited. For example, it is preferred that more than 50% by weight, more than 70% by weight, or more than 85% by weight of the hydroxyl-containing monomer used as monomer (m2) is a hydroxyalkyl acrylate. By using a hydroxyalkyl acrylate, a hydroxyl group that helps provide a crosslinking point and imparts moderate cohesiveness can be introduced into the acrylic polymer, and compared with the case of using only the corresponding methacrylic acid hydroxyalkyl ester, it is easy to obtain an adhesive with good softness and adhesion in the room temperature region.
[0079] As the example of carboxyl-containing monomers, in addition to acrylic monomers such as (meth) acrylic acid, (meth) carboxyethyl acrylate, (meth) carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid etc. can also be listed, but are not limited to these substances. As the example of carboxyl-containing monomers that can be preferably used, acrylic acid and methacrylic acid can be listed. In addition, in some ways, from the viewpoint of reducing the elastic modulus of adhesive, as carboxyl-containing monomers, compounds such as represented by the following formula (2) can be preferably used.
[0080] CH2=CR 1 -COO-R 2 -OCO-R 3 -COOH (2)
[0081] Here, R in the above formula (2) 1 R is hydrogen or methyl. 2 and R 3 is a divalent linking group (specifically, an organic group having 1 to 20 (e.g., 2 to 10, preferably 2 to 5) carbon atoms), and may be the same as or different from each other. 2 and R 3 For example, it can be a divalent aliphatic hydrocarbon group, an aromatic hydrocarbon group, or an alicyclic hydrocarbon group. 2 and R 3 It may be an alkylene group having 2 to 5 carbon atoms. Specific examples of the carboxyl group-containing monomer represented by the above formula (2) include: hexahydrophthalic acid mono(2-(meth)acryloxyethyl) ester, phthalic acid mono(2-(meth)acryloxyethyl) ester, phthalic acid (2-(meth)acryloxyethyl) ester (2-hydroxyethyl) ester, succinic acid mono(2-(meth)acryloxyethyl) ester, hexahydrophthalic acid mono(2-(meth)acryloxypropyl) ester, phthalic acid mono(2-(meth)acryloxypropyl) ester, tetrahydrophthalic acid mono(2-(meth)acryloxypropyl) ester, etc. The carboxyl group-containing monomer may be used alone or in combination of two or more. A hydroxyl group-containing monomer and a carboxyl group-containing monomer may also be used in combination.
[0082] The content of the monomer (m2) in the monomer component constituting the acrylic polymer is not particularly limited and can be set according to the purpose. In some embodiments, the content of the above-mentioned monomer (m2) can be, for example, 0.01% by weight or more, 0.1% by weight or more, or 0.5% by weight or more. From the viewpoint of obtaining a higher use effect, in some embodiments, the content of the above-mentioned monomer (m2) is preferably 0.8% by weight or more, can be 1.0% by weight or more, can also be 3.0% by weight or more, or 4.0% by weight or more. The upper limit of the content of the monomer (m2) in the monomer component is set in a manner that the total content of the monomer (m2) does not exceed 100% by weight. In some embodiments, the content of the above-mentioned monomer (m2) is, for example, 30% by weight or less or 25% by weight or less, and from the viewpoint of better exerting the effect of other monomers, it is preferably 20% by weight or less, more preferably 15% by weight or less, can be less than 12% by weight, can be less than 10% by weight, and can also be less than 7% by weight. In some preferred embodiments, from the perspective of reducing the elastic modulus of the adhesive, the content of the above-mentioned monomer (m2) is 5.0 wt % or less (for example, less than 5.0 wt %), more preferably less than 3.0 wt %, and can be less than 2.0 wt %, or less than 1.5 wt %.
[0083] In some embodiments, the total content of the monomer (m1) and the monomer (m2) in the monomer component constituting the acrylic polymer may be, for example, 21% by weight or more or 31% by weight or more, and from the viewpoint of easily and appropriately exerting the effects of these monomers, it is preferably 41% by weight or more, 51% by weight or more, 61% by weight or more, 71% by weight or more, 76% by weight or more, 81% by weight or more, 86% by weight or more, 91% by weight or more, 96% by weight or more, 99% by weight or more, or substantially 100% by weight. In addition, in some embodiments, from the viewpoint of easily and appropriately exerting the effects of monomers other than these, the total content of the monomer (m1) and the monomer (m2) in the monomer component may be, for example, 99% by weight or less, 95% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, 75% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less.
[0084] (Single (m3))
[0085] In some embodiments, the monomer component constituting the acrylic polymer may contain a monomer (m3). As the monomer (m3), a compound containing at least one aromatic ring and at least one ethylenically unsaturated group in one molecule is used. The monomer (m3) may be used alone or in combination of two or more.
[0086] Examples of the ethylenically unsaturated group possessed by the monomer (m3) include: (meth)acryloyl, vinyl, (meth)allyl, etc. From the viewpoint of polymerization reactivity, a (meth)acryloyl group is preferred, and from the viewpoint of low elastic modulus and adhesion, an acryloyl group is more preferred. From the viewpoint of low elastic modulus of the adhesive, as the monomer (m3), a compound having 1 ethylenically unsaturated group contained in one molecule (i.e., a monofunctional monomer) is preferably used.
[0087] The number of aromatic rings contained in one molecule of the compound used as the monomer (m3) may be 1 or more than 2. The upper limit of the number of the aromatic rings is not particularly limited, and may be, for example, 16 or less. In some embodiments, from the viewpoints of the ease of preparation of the adhesive composition, the transparency of the adhesive, etc., the number of the aromatic rings may be, for example, 12 or less, preferably 8 or less, more preferably 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less.
[0088] The aromatic ring possessed by the compound used as the monomer (m3) may be a carbon ring, for example, a benzene ring (which may be a benzene ring constituting a part of a biphenyl structure or a fluorene structure); a condensed ring of a naphthalene ring, an indene ring, an azulene ring, an anthracene ring, a phenanthrene ring, etc.; or a heterocyclic ring (heteroelement ring), for example, a pyridine ring, a pyrimidine ring, a pyridazine ring, a pyrazine ring, a triazine ring, a pyrrole ring, a pyrazole ring, an imidazole ring, a triazole ring, Azole ring, iso The heteroatoms included as the ring-constituting atoms in the above heterocyclic rings may be, for example, one or more selected from the group consisting of nitrogen, sulfur and oxygen. In some embodiments, the heteroatoms constituting the above heterocyclic rings may be one or both of nitrogen and sulfur. The monomer (m3) may have a structure in which one or more carbon rings are fused with one or more heterocyclic rings, such as a dinaphthothiophene structure.
[0089] The above-mentioned aromatic ring (preferably a carbocyclic ring) may have one or more substituents on the ring-constituting atoms, or may not have substituents. In the case of having a substituent, as the substituent, alkyl, alkoxy, aryloxy, hydroxyl, halogen atoms (fluorine atoms, chlorine atoms, bromine atoms, etc.), hydroxyalkyl, hydroxyalkyloxy, glycidoxy, etc. can be exemplified, but are not limited to these groups. In the substituent containing carbon atoms, the number of carbon atoms contained in the substituent is preferably 1 to 4, more preferably 1 to 3, for example, it can be 1 or 2. In some embodiments, the above-mentioned aromatic ring can be an aromatic ring that has no substituents on the ring-constituting atoms, or has one or more substituents selected from the group consisting of alkyl, alkoxy and halogen atoms (such as bromine atoms) on the ring-constituting atoms. It should be noted that the aromatic ring possessed by the monomer (m3) having a substituent on its ring-constituting atoms means that the aromatic ring has a substituent other than a substituent having an ethylenically unsaturated group.
[0090] The aromatic ring and the ethylenically unsaturated group may be directly bonded or bonded via a connecting group (connecting group). The connecting group may be, for example, a group selected from an alkylene group, an oxyalkylene group, a poly(oxyalkylene) group, a phenyl group, an alkylphenyl group, an alkoxyphenyl group, a group having a structure in which one or more hydrogen atoms in these groups are replaced by a hydroxyl group (for example, a hydroxyalkylene group), an oxy group (-O- group), a thiooxy group (-S- group), etc., or a group having one or more structures. In some embodiments, an aromatic ring-containing monomer having a structure in which an aromatic ring is directly bonded to an ethylenically unsaturated group or bonded via a connecting group selected from the group consisting of an alkylene group, an oxyalkylene group and a poly(oxyalkylene) group may be preferably used. The number of carbon atoms in the alkylene group and the oxyalkylene group is preferably 1 to 4, more preferably 1 to 3, for example, 1 or 2. The number of repetitions of the oxyalkylene unit in the poly(oxyalkylene) group may be, for example, 2 to 3.
[0091] As examples of compounds that can be preferably used as monomers (m3), aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds can be cited. Aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds can be used alone or in combination of two or more. One or two or more aromatic ring-containing (meth)acrylates can be used in combination with one or two or more aromatic ring-containing vinyl compounds.
[0092] In some embodiments, as a monomer (m3), from the viewpoint of easily obtaining a high refractive index effect, a monomer having two or more aromatic rings (preferably a carbon ring) in one molecule can be preferably used. As examples of monomers having two or more aromatic rings in one molecule (monomers containing multiple aromatic rings), there can be listed: monomers having a structure in which two or more non-condensed aromatic rings are bonded via a connecting group, monomers having a structure in which two or more non-condensed aromatic rings are directly (i.e., not via other atoms) chemically bonded, monomers having a condensed aromatic ring structure, monomers having a fluorene structure, monomers having a dinaphthothiophene structure, monomers having a dibenzothiophene structure, etc. Monomers containing multiple aromatic rings can be used alone or in combination of two or more.
[0093] The linking group may be, for example, an oxy group (-O-), a thiooxy group (-S-), an oxyalkylene group (e.g., -O-(CH2) n -alkyl, wherein n is 1 to 3, preferably 1), thioalkylene (e.g. -S-(CH2) n -alkyl, wherein n is 1 to 3, preferably 1), straight chain alkylene (i.e. -(CH2) n - group, wherein n is 1 to 6, preferably 1 to 3), a group in which the alkylene in the above-mentioned oxyalkylene, the above-mentioned thioalkylene and the above-mentioned linear alkylene is partially or completely halogenated, etc. From the viewpoint of the flexibility of the adhesive, etc., preferred examples of the above-mentioned connecting group include oxy, thiooxy, oxyalkylene and linear alkylene. Specific examples of monomers having a structure in which two or more non-condensed aromatic rings are bonded via a connecting group include: phenoxybenzyl (meth)acrylate (e.g., m-phenoxybenzyl (meth)acrylate), phenylthiobenzyl (meth)acrylate, benzylbenzyl (meth)acrylate, etc.
[0094] The monomer having a structure in which two or more non-condensed aromatic rings are directly chemically bonded may be, for example, a (meth)acrylate containing a biphenyl structure, a (meth)acrylate containing a triphenyl structure, a vinyl-containing biphenyl, etc. Specific examples include o-phenylphenol (meth)acrylate, biphenyl methyl (meth)acrylate, etc.
[0095] Examples of the monomer having a condensed aromatic ring structure include naphthalene ring-containing (meth)acrylates, anthracene ring-containing (meth)acrylates, vinyl-containing naphthalene, vinyl-containing anthracene, etc. Specific examples include 1-naphthylmethyl (meth)acrylate (also known as 1-naphthylmethyl (meth)acrylate), hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, and 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate.
[0096] Specific examples of the monomer having a fluorene structure include 9,9-bis(4-hydroxyphenyl)fluorene(meth)acrylate, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene(meth)acrylate, etc. It should be noted that the monomer having a fluorene structure includes a structural portion in which two benzene rings are directly chemically bonded, and is therefore included in the concept of the monomer having a structure in which two or more non-condensed aromatic rings are directly chemically bonded.
[0097] Examples of the above-mentioned monomer having a dinaphthothiophene structure include dinaphthothiophene containing a (meth)acryloyl group, dinaphthothiophene containing a vinyl group, and dinaphthothiophene containing a (meth)allyl group. Specific examples include (meth)acryloyloxymethyl dinaphthothiophene (for example, CH2CH(R) is bonded to the 5-position or 6-position of the dinaphthothiophene ring); 1 )C(O)OCH2-. Here, R 1 is a hydrogen atom or a methyl group. ), (meth)acryloyloxyethyl dinaphthothiophene (for example, CH2CH(R) is bonded to the 5-position or 6-position of the dinaphthothiophene ring) 1 )C(O)OCH(CH3)- or CH2CH(R 1 )C(O)OCH2CH2-. Here, R 1 is a hydrogen atom or a methyl group. ), vinyl dinaphthothiophene (for example, a compound having a structure in which a vinyl group is bonded to the 5-position or 6-position of the naphthothiophene ring), (methyl)allyloxy dinaphthothiophene, etc. It should be noted that the monomer having a dinaphthothiophene structure is included in the concept of the monomer having a fused aromatic ring structure because it contains a naphthalene structure and also has a structure in which a thiophene ring is fused to two naphthalene structures.
[0098] Examples of the monomer having a dibenzothiophene structure include (meth)acryloyl-containing dibenzothiophene, vinyl-containing dibenzothiophene, etc. It should be noted that the monomer having a dibenzothiophene structure is included in the concept of the monomer having a fused aromatic ring structure because it has a structure in which a thiophene ring is fused with two benzene rings.
[0099] It should be noted that neither the dinaphthothiophene structure nor the dibenzothiophene structure belongs to a structure in which two or more non-condensed aromatic rings are directly chemically bonded.
[0100] In some preferred embodiments, as monomer (m3), a monomer having one aromatic ring (preferably a carbon ring) in one molecule can be used. A monomer having one aromatic ring in one molecule (a monomer containing a single aromatic ring) can, for example, contribute to the improvement of the flexibility of the adhesive, the adjustment of the adhesive properties, the improvement of the transparency, etc. A monomer containing a single aromatic ring can be used alone or in combination of two or more. In some embodiments, from the viewpoint of increasing the refractive index of the adhesive, a monomer having one aromatic ring in one molecule is preferably used in combination with a monomer containing multiple aromatic rings.
[0101] Examples of monomers having one aromatic ring in one molecule include: (meth)acrylates containing a carbon aromatic ring, such as benzyl (meth)acrylate, methoxybenzyl (meth)acrylate, phenyl (meth)acrylate, ethoxylated phenol (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxybutyl (meth)acrylate, methylphenyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and benzyl (meth)acrylate chloride; (meth)acrylates containing a carbon aromatic ring, such as 2-(4,6-dibromo-2-sec-butylphenoxy)ethyl (meth)acrylate, 2-(4,6-dibromo-2 (Meth)acrylates containing bromine-substituted aromatic rings, such as 6-(4,6-dibromo-2-sec-butylphenoxy)ethyl (meth)acrylate, 6-(4,6-dibromo-2-sec-butylphenoxy)hexyl (meth)acrylate, 2,6-dibromo-4-nonylphenyl acrylate, and 2,6-dibromo-4-dodecylphenyl acrylate; vinyl compounds containing carbon aromatic rings, such as styrene, α-methylstyrene, vinyltoluene, and tert-butylstyrene; N-vinylpyridine, N-vinylpyrimidine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyl Compounds such as azoles having a vinyl substituent on a heteroaromatic ring; etc.
[0102] As monomer (m3), a monomer having a structure in which an oxyethylene chain is sandwiched between the ethylenically unsaturated group and the aromatic ring in the various aromatic ring-containing monomers described above can be used. Such a monomer having an oxyethylene chain sandwiched between the ethylenically unsaturated group and the aromatic ring can be understood as an ethoxylate of the original monomer. The number of repetitions of the oxyethylene unit (-CH2CH2O-) in the above-mentioned oxyethylene chain is typically 1 to 4, preferably 1 to 3, more preferably 1 to 2, for example 1. Specific examples of ethoxylated aromatic ring-containing monomers include: ethoxylated o-phenylphenol (meth)acrylate, ethoxylated nonylphenol (meth)acrylate, ethoxylated cresol (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol di(meth)acrylate, and the like.
[0103] The content of the monomer containing multiple aromatic rings in the monomer (m3) is not particularly limited, for example, it can be 5% by weight or more, 25% by weight or more, 40% by weight or more, or 50% by weight or more. From the perspective of easily obtaining a higher refractive index, it can be 70% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of the monomer (m3) can be a monomer containing multiple aromatic rings. That is, as a monomer (m3), only one or more monomers containing multiple aromatic rings can be used. In addition, in some embodiments, for example, considering the balance between high refractive index and flexibility, and considering the balance with adhesive force when necessary, the content of the monomer containing multiple aromatic rings in the monomer (m3) can be less than 100% by weight, can be 98% by weight or less, can be 90% by weight or less, can be 80% by weight or less, can be 70% by weight or less, can be 65% by weight or less, can be 50% by weight or less, can be 25% by weight or less, can be 10% by weight or less. The technology disclosed herein can be implemented in a manner in which the content of the monomer containing multiple aromatic rings in the monomer (m3) is less than 5% by weight. It is also possible not to use the monomer containing multiple aromatic rings.
[0104] The content of monomers containing aromatic rings in the monomer components constituting the acrylic polymer is not particularly limited and can be set in a manner that allows for an adhesive having both the desired refractive index and elastic modulus to be achieved. The content of monomers containing multiple aromatic rings in the above-mentioned monomer components can be, for example, 3% by weight or more, 10% by weight or more, or 20% by weight or more. Considering the balance between high refractive index and flexibility, and, if necessary, the balance with adhesive force, it is appropriate that the content of monomers containing multiple aromatic rings in the above-mentioned monomer components is about 60% by weight or less, and can be 50% by weight or less (for example, less than 50% by weight), 40% by weight or less, 25% by weight or less, 15% by weight or less, or 5% by weight or less. The technology disclosed herein can also be implemented in a manner that the content of monomers containing multiple aromatic rings in the above-mentioned monomer components is less than 3% by weight. Monomers containing multiple aromatic rings may also not be used.
[0105] The content of the monomer containing a single aromatic ring in the monomer (m3) is not particularly limited, for example, it can be 5% by weight or more, 25% by weight or more, 40% by weight or more, or 50% by weight or more. From the perspective of easily obtaining a higher refractive index, it can be 70% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of the monomer (m3) can be a monomer containing a single aromatic ring. That is, as a monomer (m3), only one or more monomers containing a single aromatic ring can be used. In addition, in some embodiments, for example, considering the balance between high refractive index and flexibility, and considering the balance with adhesive force when necessary, the content of the monomer containing a single aromatic ring in the monomer (m3) can be less than 100% by weight, can be 98% by weight or less, can be 90% by weight or less, can be 80% by weight or less, can be 70% by weight or less, can be 65% by weight or less, can be 50% by weight or less, can be 25% by weight or less, can be 10% by weight or less. The technology disclosed herein can also be implemented in a mode where the content of the monomer containing a single aromatic ring in the monomer (m3) is less than 5% by weight. It is also possible not to use the monomer containing a single aromatic ring.
[0106] The content of monomers containing a single aromatic ring in the monomer components constituting the acrylic polymer is not particularly limited and can be set in a manner that can achieve an adhesive that takes into account both the desired refractive index and flexibility. The content of monomers containing a single aromatic ring in the above-mentioned monomer components can be, for example, 3% by weight or more, 10% by weight or more, or 20% by weight or more. Considering the balance between high refractive index and flexibility, and the balance with adhesive force when necessary, it is appropriate that the content of monomers containing a single aromatic ring in the above-mentioned monomer components is about 60% by weight or less, and can be 50% by weight or less (for example, less than 50% by weight), 40% by weight or less, 25% by weight or less, 15% by weight or less, or 5% by weight or less. The technology disclosed herein can be implemented in a manner that the content of monomers containing a single aromatic ring in the above-mentioned monomer components is less than 3% by weight. Monomers containing a single aromatic ring may also not be used.
[0107] In some embodiments of the technology disclosed herein, as at least a part of the monomer (m3), a high refractive index monomer can be preferably used. Here, "high refractive index monomer" refers to a monomer whose refractive index is, for example, about 1.510 or more, preferably about 1.530 or more, and more preferably about 1.550 or more. In some embodiments, the refractive index of the high refractive index monomer can be more than 1.570, can be more than 1.600, can be more than 1.620, can be more than 1.650, more than 1.675 or more than 1.700. The upper limit of the refractive index of the high refractive index monomer is not particularly limited. From the perspective of the ease of preparation of the adhesive composition and the flexibility suitable as an adhesive, for example, it is less than 3.000, can be less than 2.500, can be less than 2.000, can be less than 1.900, can be less than 1.850, can be less than 1.800, can be less than 1.750, can be less than 1.700. The high refractive index monomer can be used alone or in combination of two or more.
[0108] It should be noted that the refractive index of the monomer is measured using an Abbe refractometer at a measurement wavelength of 589 nm and a measurement temperature of 25° C. As the Abbe refractometer, a model "DR-M4" manufactured by ATAGO or its equivalent can be used. When a nominal value of the refractive index at 25° C. is provided by a manufacturer, the nominal value can be used.
[0109] As the above-mentioned high refractive index monomer, a substance having a corresponding refractive index can be appropriately adopted from the compounds included in the concept of the aromatic ring-containing monomer (m3) disclosed herein (for example, the compounds and compound groups exemplified above). Specific examples include: m-phenoxybenzyl acrylate (refractive index: 1.566, Tg of homopolymer: -35°C), 1-naphthylmethyl acrylate (refractive index: 1.595, Tg of homopolymer: 31°C), ethoxylated o-phenylphenol acrylate (number of repetitions of oxyethylene units: 1, refractive index: 1.578), benzyl acrylate (refractive index (nD20): 1.519, Tg of homopolymer: 6°C), phenoxyethyl acrylate (refractive index (nD20): 1.517, Tg of homopolymer: 2°C), phenoxydiethylene glycol acrylate (refractive index: 1.510, Tg of homopolymer: 31°C). g: -35°C), 6-acryloyloxymethyl dinaphthothiophene (6MDNTA, refractive index: 1.737), 6-methacryloyloxymethyl dinaphthothiophene (6MDNTMA, refractive index: 1.726), 5-acryloyloxyethyl dinaphthothiophene (5EDNTA, refractive index: 1.786), 6-acryloyloxyethyl dinaphthothiophene (6EDNTA, refractive index: 1.722), 6-vinyl dinaphthothiophene (6VDNT, refractive index: 1.802), 5-vinyl dinaphthothiophene (abbreviation: 5VDNT, refractive index: 1.793), etc., but not limited to these substances.
[0110] The content of the high refractive index monomer (i.e., an aromatic ring-containing monomer having a refractive index of about 1.510 or more, preferably about 1.530 or more, and more preferably about 1.550 or more) in the monomer (m3) is not particularly limited, and may be, for example, 5% by weight or more, 25% by weight or more, 35% by weight or more, or 40% by weight or more. In some embodiments, from the perspective of easily obtaining a higher refractive index, the content of the high refractive index monomer in the monomer (m3) may be, for example, 50% by weight or more, preferably 70% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of the monomer (m3) may be a high refractive index monomer. In addition, in some embodiments, for example, from the perspective of balancing high refractive index and softness and, if necessary, balancing adhesive strength, the content of high refractive index monomer in monomer (m3) can be less than 100 weight %, can be less than 98 weight %, can be less than 90 weight %, can be less than 80 weight %, or can be less than 65 weight %.
[0111] The content of the high refractive index monomer in the monomer component constituting the acrylic polymer is not particularly limited, and can be set in a manner that can realize the adhesive of taking into account the desired refractive index and elastic modulus. In addition, when necessary, it can be further considered to take into account adhesive properties (such as adhesive force, etc.) and / or optical properties (such as total light transmittance, haze value, etc.) to set. The content of the high refractive index monomer in the above-mentioned monomer component can be, for example, more than 3 % by weight, more than 10 % by weight, or more than 20 % by weight. From taking into account high refractive index and flexibility in a balanced manner, when necessary, the viewpoint of also taking into account adhesive force in a balanced manner is considered, and the content of the high refractive index monomer in the above-mentioned monomer component is appropriate to be about 60 % by weight or less, can be 50 % by weight or less (such as less than 50 % by weight), can be 40 % by weight or less, can be 25 % by weight or less, can be 15 % by weight or less, can be 5 % by weight or less, can be less than 3 % by weight. It is also possible not to use a high refractive index monomer.
[0112] In some preferred embodiments, an aromatic ring-containing monomer (hereinafter sometimes referred to as "monomer L") having a homopolymer Tg of 10°C or less is used as at least a part of the monomer (m3). When the content of the aromatic ring-containing monomer (m3) in the monomer component is increased (especially an aromatic ring-containing monomer (m3) equivalent to at least one of the above-mentioned monomers containing multiple aromatic rings, monomers containing a single aromatic ring, and high refractive index monomers), the storage modulus G' of the adhesive generally tends to increase. By using monomer L as part or all of the monomer (m3), the increase in the storage modulus G' can be suppressed. In this way, the refractive index can be improved while maintaining a low elastic modulus better. The Tg of monomer L can be, for example, below 5°C, below 0°C, below -10°C, below -20°C, or below -25°C. The lower limit of the Tg of monomer L is not particularly limited. Considering the balance with the refractive index improvement effect, in some embodiments, the Tg of monomer L can be, for example, above -70°C, above -55°C, or above -45°C. In some other embodiments, the Tg of the monomer L may be, for example, above -30°C, above -10°C, above 0°C, or above 3°C. The monomer L may be used alone or in combination of two or more.
[0113] As the monomer L, a substance having the above Tg can be appropriately adopted from the compounds included in the concept of the aromatic ring-containing monomer (m3) disclosed herein (e.g., the compounds and compound groups exemplified above). Preferred examples of aromatic ring-containing monomers that can be used as monomer L include: m-phenoxybenzyl acrylate (homopolymer Tg: -35°C), benzyl acrylate (homopolymer Tg: 6°C), phenoxyethyl acrylate (homopolymer Tg: 2°C), and phenoxydiethylene glycol acrylate (homopolymer Tg: -35°C).
[0114] The content of monomer L in monomer (m3) is not particularly limited, for example, it can be 5% by weight or more, 25% by weight or more, or 40% by weight or more. In some embodiments, from the perspective of easily obtaining an adhesive that takes into account both high refractive index and softness at a higher level, the content of monomer L in monomer (m3) can be, for example, 50% by weight or more, and from the perspective of low elastic modulus, it is preferably 60% by weight or more, 70% by weight or more, 75% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. It can be that substantially 100% by weight of monomer (m3) is monomer L. In addition, in some embodiments, for example, from the perspective of balancing high refractive index and softness, and also balancing adhesive force when necessary, the content of monomer L in monomer (m3) can be less than 100% by weight, 98% by weight or less, 90% by weight or less, 80% by weight or less, or 65% by weight or less.
[0115] The content of monomer L in the monomer component constituting the acrylic polymer can be, for example, more than 3% by weight, more than 10% by weight, or more than 20% by weight. From the perspective of balanced consideration of high refractive index and flexibility, and balanced consideration of adhesive strength when necessary, it is appropriate that the content of monomer L in the above-mentioned monomer component is about 60% by weight or less, can be 50% by weight or less (for example, less than 50% by weight), can be 40% by weight or less, can be 25% by weight or less, can be 15% by weight or less, can be 5% by weight or less, or can be less than 3% by weight. Monomer L may not be used.
[0116] In some embodiments, the aromatic ring-containing monomer (m3) can be preferably selected from compounds that do not contain a structure in which two or more non-condensed aromatic rings are directly chemically bonded (e.g., a biphenyl structure). For example, it is preferably an acrylic polymer composed of monomer components composed of a composition in which the content of a compound containing a structure in which two or more non-condensed aromatic rings are directly chemically bonded is less than 5% by weight (more preferably less than 3% by weight, which can be 0% by weight). From the perspective of achieving a more balanced balance between high refractive index and softness, and, if necessary, a more balanced balance between adhesive strength, it is advantageous to limit the amount of compounds containing a structure obtained by direct chemical bonding of two or more non-condensed aromatic rings.
[0117] The content of the monomer (m3) in the monomer component constituting the acrylic polymer is not particularly limited, and can be set in a manner that can realize an adhesive having a desired refractive index and elastic modulus, as well as adhesive properties (such as adhesive strength, etc.) and / or optical properties (such as total light transmittance, haze value, etc.). The content of the monomer (m3) in the above-mentioned monomer component can be, for example, more than 1% by weight, more than 3% by weight, more than 5% by weight, more than 10% by weight, more than 15% by weight, or more than 20% by weight. From the viewpoint of obtaining a higher effect, in some ways, the content of the monomer (m3) in the above-mentioned monomer component can be more than 25% by weight, or more than 30% by weight, more than 40% by weight, more than 45% by weight, or more than 50% by weight. The content of the monomer (m3) in the above-mentioned monomer component is typically less than 100 weight %, less than about 75 weight % (for example, greater than or equal to 0 weight % and less than 75 weight %) is appropriate, preferably about 60 weight % or less, can be 50 weight % or less (for example, less than 50 weight %), can be 40 weight % or less, can be 25 weight % or less, can be 15 weight % or less, can be 5 weight % or less, can be less than 3 weight %. The adhesive disclosed herein can be preferably implemented in a manner that the monomer component constituting the acrylic polymer does not include the monomer (m3).
[0118] (Other monomers)
[0119] The monomer components constituting the acrylic polymer may contain monomers other than the above-mentioned monomers (m1), (m2), and (m3) (hereinafter referred to as "other monomers") as required. The above-mentioned other monomers may be used, for example, for the purpose of adjusting the Tg of the acrylic polymer, adjusting the adhesive performance, improving the compatibility in the adhesive layer, etc. The above-mentioned other monomers may be used alone or in combination of two or more.
[0120] As examples of the above-mentioned other monomers, monomers having functional groups other than hydroxyl and carboxyl groups (functional group-containing monomers) can be cited. For example, as other monomers that can improve the cohesive force and heat resistance of the adhesive, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyano group-containing monomers, etc. can be cited. In addition, as monomers that can introduce functional groups that can become crosslinking bases into acrylic polymers, or help improve the adhesion to the adherend and the compatibility within the adhesive, amide group-containing monomers (such as (methyl) acrylamide, N-hydroxymethyl (methyl) acrylamide, etc.), amino group-containing monomers (such as (methyl) acrylate aminoethyl, (methyl) acrylate N, N-dimethylaminoethyl, etc.), monomers having a ring containing a nitrogen atom (such as N-vinyl-2-pyrrolidone, N-(methyl) acryloyl morpholine, etc.), imide group-containing monomers, epoxy group-containing monomers, ketone group-containing monomers, isocyanate group-containing monomers, alkoxysilyl group-containing monomers, etc. can be cited. It should be noted that, among the monomers having a nitrogen atom-containing ring, there is a substance such as N-vinyl-2-pyrrolidone which is also an amide group-containing monomer. The same applies to the relationship between the above-mentioned monomers having a nitrogen atom-containing ring and the amino group-containing monomer.
[0121] As other monomers that can be used in addition to the above-mentioned functional group-containing monomers, there are listed: vinyl ester monomers such as vinyl acetate; (meth)acrylates containing non-aromatic rings such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; olefin monomers such as ethylene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride; alkoxy-containing monomers such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and ethoxyethoxyethyl (meth)acrylate; vinyl ether monomers such as methyl vinyl ether; and the like.
[0122] In some embodiments, for the purpose of low elastic modulus of the adhesive (especially low elastic modulus in low temperature areas), improvement of elongation deformability (for example, improvement of elongation at break), etc., it is preferred to use alkoxy-containing monomers as the above-mentioned other monomers. Alkoxy-containing monomers can also contribute to the reduction of haze and the improvement of adhesion. Preferred examples of alkoxy-containing monomers include alkoxy-containing acrylates such as methoxyethyl acrylate (MEA) (Tg of homopolymer: -50°C), ethoxyethoxyethyl acrylate (alias: ethyl carbitol acrylate, homopolymer Tg: -67°C), etc. The content of alkoxy-containing monomers in the monomer components constituting the acrylic polymer can be, for example, 1% by weight or more, 3% by weight or more, and from the viewpoint of obtaining a higher effect, 5% by weight or more, 10% by weight or more, or 15% by weight or more. In addition, the content of the alkoxy-containing monomer in the monomer component can be, for example, 40% by weight or less (e.g., 0 to 40% by weight). From the viewpoint of easily achieving a balance between a high refractive index and the characteristics as an adhesive, it is advantageous to be 35% by weight or less, preferably 30% by weight or less, and can be 25% by weight or less, or can be 22% by weight or less.
[0123] When using the above-mentioned other monomers, the amount used is not particularly limited and can be appropriately set within the range where the total amount of the monomer component does not exceed 100% by weight. In some embodiments, from the perspective of easily taking into account the balance between high refractive index and the characteristics as an adhesive, the content of the above-mentioned other monomers in the monomer component can be, for example, about 45% by weight or less (e.g., 0 to 45% by weight), about 40% by weight or less is appropriate, about 35% by weight or less, about 30% by weight or less, about 25% by weight or less, about 20% by weight or less, about 10% by weight or less, about 5% by weight or less, or about 1% by weight or less. The technology disclosed herein can preferably be implemented in a manner that the monomer component does not substantially contain the above-mentioned other monomers.
[0124] In some embodiments, the monomer components constituting the acrylic polymer may be a composition in which the amount of the monomer containing a methacryloyl group is suppressed to a prescribed level or less. The amount of the methacryloyl-containing monomer in the monomer components may be, for example, less than 5% by weight, less than 3% by weight, less than 1% by weight, or less than 0.5% by weight. From the perspective of achieving an adhesive that balances flexibility, adhesion, and a high refractive index, it is advantageous to limit the amount of the monomer containing a methacryloyl group in this way. The monomer components constituting the acrylic polymer may be a composition that does not contain a methacryloyl-containing monomer (e.g., a composition that contains only acryl-containing monomers).
[0125] In some ways, in the monomer composition constituting acrylic polymer, from the viewpoint of suppressing the coloring or discoloration (such as yellowing) of adhesive, the use amount of carboxyl-containing monomer is limited. The use amount of carboxyl-containing monomer in the monomer composition can be, for example, less than 1 weight %, less than 0.5 weight %, less than 0.3 weight %, less than 0.1 weight %, less than 0.05 weight %. From the viewpoint of suppressing the corrosion of the metal material (such as metal wiring, metal film etc. that may be present on adherend) that may contact or be configured close to adhesive disclosed herein, it is advantageous to limit the use amount of carboxyl-containing monomer in this way. The technology disclosed herein can be implemented in a manner that the monomer composition constituting acrylic polymer does not contain carboxyl-containing monomer.
[0126] For the same reason, in some embodiments, it is preferred to limit the amount of monomers having acidic functional groups (including sulfonic acid groups, phosphoric acid groups, etc. in addition to carboxyl groups) in the monomer components constituting the acrylic polymer. As the amount of monomers containing acidic functional groups in the monomer components of this embodiment, the preferred amount of carboxyl group-containing monomers described above can be applied. The technology disclosed herein can be preferably implemented in a manner in which the monomer components do not contain monomers containing acidic groups (i.e., the acrylic polymer is acid-free).
[0127] (Method for preparing acrylic polymer)
[0128] In the technology disclosed herein, the method for obtaining an acrylic polymer composed of such monomer components is not particularly limited, and various polymerization methods known as synthetic methods of acrylic polymers such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately adopted. For example, solution polymerization can be preferably adopted. The polymerization temperature when performing solution polymerization can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be, for example, about 20°C to about 170°C (typically about 40°C to about 140°C).
[0129] The solvent (polymerization solvent) used for solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc. can be used.
[0130] The initiator used for the polymerization can be appropriately selected from the polymerization initiators known in the past according to the type of polymerization method. For example, one or more of the azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. As other examples of polymerization initiators, there can be listed: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds; etc. As other examples of polymerization initiators, redox initiators based on the combination of peroxides and reducing agents can be listed. The polymerization initiator can be used alone or in combination of two or more. The amount of the polymerization initiator used can be the usual amount, for example, it can be selected from the range of about 0.005 parts by weight to about 1 part by weight (typically about 0.01 parts by weight to about 1 part by weight) relative to 100 parts by weight of the monomer component.
[0131] In the above-mentioned polymerization, various chain transfer agents known in the past can be used as needed. For example, thiols such as n-dodecyl mercaptan, tert-dodecyl mercaptan, thioglycolic acid, and α-thioglycerol can be used. Alternatively, a chain transfer agent that does not contain a sulfur atom (non-sulfur chain transfer agent) can be used. Examples of non-sulfur chain transfer agents include: anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenes such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; etc. Chain transfer agents can be used alone or in combination of two or more. When a chain transfer agent is used, the amount of the chain transfer agent used can be, for example, about 0.01 parts by weight to about 1 part by weight relative to 100 parts by weight of the monomer component.
[0132] (Glass transition temperature Tg of base polymer P )
[0133] In the technology disclosed herein, the monomer component constituting the base polymer (eg, acrylic polymer) of the adhesive preferably has a glass transition temperature Tg of 0.0447 W / cm3 based on the composition of the monomer component. P The glass transition temperature Tg is about 10°C or less. P It is preferably 0°C or less (e.g., less than 0°C), more preferably -10°C or less, further preferably -20°C or less, can be -25°C or less, can be -30°C or less, can be -35°C or less, can be -40°C or less, can be -45°C or less, can be -50°C or less, can be -55°C or less, can be -57°C or less. From the perspective of the low elastic modulus of the adhesive, the glass transition temperature Tg P A low glass transition temperature Tg P There is no particular lower limit on the glass transition temperature Tg. PFor example, it may be -70°C or higher. From the viewpoint of easily realizing an adhesive having moderate cohesiveness, it is advantageous to be -65°C or higher. It may be -60°C or higher, or -55°C or higher. By using a glass transition temperature Tg in the above range, P A base polymer having a composition of can satisfactorily realize an adhesive having both a high refractive index and flexibility.
[0134] Here, unless otherwise specified, the glass transition temperature Tg P It refers to the glass transition temperature obtained by the Fox equation based on the composition of the above-mentioned monomer components. The Fox equation is shown below. The Fox equation is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing the monomers constituting the copolymer.
[0135] 1 / Tg=Σ(Wi / Tgi)
[0136] In the above Fox equation, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).
[0137] As the glass transition temperature of the homopolymer used in the calculation of Tg, the value recorded in the known materials such as "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) is used. For monomers for which multiple values are recorded in the above-mentioned polymer handbook, the highest value is adopted. In the case where the Tg of the homopolymer is not recorded in the known materials, the value obtained by the determination method recorded in Japanese Patent Application Publication No. 2007-51271 is used.
[0138] (Weight average molecular weight of base polymer)
[0139] The weight average molecular weight (Mw) of the base polymer (e.g., acrylic polymer) is not particularly limited, and may be, for example, about 30×10 4 Above, it can be about 40×10 4 Above, it can also be about 50×10 4 By using a base polymer having an Mw of a predetermined value or more, it is easy to obtain a moderate cohesive force capable of exerting the desired adhesive properties and elongation deformation properties. In some embodiments, the Mw of the base polymer is 55×10 4 The above is appropriate, for 60×10 4 The above is favorable, preferably 70×10 4 More preferably 80×10 4 Above, it can be 90×10 4Above, it can be 100×10 4 Above, it can also be 120×10 4 From the ease of stably retaining additives (e.g., additives (H RO ), preferably additive (A), etc.), from the viewpoint of improving the transparency of the adhesive, it is advantageous that the Mw of the base polymer is not too low. The upper limit of the Mw of the base polymer is, for example, about 500×10 4 From the viewpoint of adhesive performance, it is preferably about 400×10 4 Less than (more preferably about 300×10 4 Below, for example, about 200×10 4 The range of 170×10 4 Below, about 150×10 4 Below or about 130×10 4 the following.
[0140] The Mw of the base polymer (eg, acrylic polymer) can be determined by gel permeation chromatography (GPC) in terms of polystyrene. Specifically, it can be determined by measuring under the following conditions using a GPC measuring apparatus with a trade name of "HLC-8220GPC" (manufactured by Tosoh Corporation).
[0141] [GPC measurement conditions]
[0142] Sample concentration: 0.2 wt% (tetrahydrofuran solution)
[0143] Sample injection volume: 10 μL
[0144] Eluent: Tetrahydrofuran (THF)
[0145] Flow rate: 0.6 mL / min
[0146] Column temperature (measurement temperature): 40°C
[0147] column:
[0148] Sample column: 1 TSKguardcolumn SuperHZ-H + 2 TSKgel SuperHZM-H (manufactured by Tosoh Corporation)
[0149] Reference column: 1 piece, trade name "TSKgel SuperH-RC" (manufactured by Tosoh Corporation)
[0150] Detector: Differential Refractometer (RI)
[0151] Standard sample: polystyrene
[0152] (High refractive index additive (HRO ))
[0153] In some embodiments, the above adhesive (eg, acrylic adhesive) further comprises a high refractive index additive (H RO ) (hereinafter, sometimes referred to as "additive (H RO )”). Here, the above “H RO ” indicates an organic material with a high refractive index. RO ), it is possible to realize an adhesive that more appropriately takes into account both the refractive index and the adhesive properties (peel strength, flexibility, etc.). RO ) The organic material used may be a polymer or a non-polymer. In addition, it may have a polymerizable functional group or may not have a polymerizable functional group.
[0154] As an additive (H RO ), it is preferred to use a compound that is at least one of a compound having a ring containing a double bond and a compound having a heterocyclic ring (which may be a ring containing a double bond), that is, a compound containing a ring belonging to at least one of a heterocyclic ring and a ring containing a double bond. By containing such a compound, the refractive index of the adhesive can be efficiently improved. The above compound is preferably an asymmetric structure. This can be more advantageous from the perspectives of, for example, the ease of preparation of the adhesive composition (for example, solubility in the solvent used in the solvent-type adhesive composition), compatibility in the adhesive, etc.
[0155] Additives (H RO The double bond-containing ring possessed by the additive (H) may be a conjugated double bond-containing ring (typically an aromatic ring) or a non-conjugated double bond-containing ring. RO ) preferably has at least one ring selected from an aromatic ring and a heterocyclic ring (heterocyclic ring) as a ring containing a double bond. The heterocyclic ring may have a structure contained in an aromatic ring, or may have a heterocyclic structure containing a double bond different from the aromatic ring. RO ) may have a double bond-containing ring (typically an aromatic ring), which may be a carbon ring, such as a benzene ring (which may be a benzene ring constituting a part of a biphenyl structure or a fluorene structure); a condensed ring of a naphthalene ring, an indene ring, an azulene ring, an anthracene ring, a phenanthrene ring, etc.; or a heterocyclic ring, such as a pyridine ring, a pyrimidine ring, a pyridazine ring, a pyrazine ring, a triazine ring, a pyrrole ring, a pyrazole ring, an imidazole ring, a triazole ring, Azole ring, iso The heteroatoms included in the heterocyclic ring as the ring-constituting atoms may be, for example, one or more selected from nitrogen, sulfur and oxygen. In some embodiments, the heteroatoms constituting the heterocyclic ring may be one or both of nitrogen and sulfur. RO ) may have a structure in which one or two or more carbon rings are fused with one or two or more hetero rings, such as a dinaphthothiophene structure.
[0156] In some embodiments, as an additive (H RO ), from the viewpoint of easily obtaining a high refractive index-enhancing effect, it is preferable to use an organic compound having two or more aromatic rings in one molecule (hereinafter also referred to as "a compound containing multiple aromatic rings". The compound containing multiple aromatic rings may have a polymerizable functional group such as an ethylenically unsaturated group, or may not have a polymerizable functional group such as an ethylenically unsaturated group. In addition, the compound containing multiple aromatic rings may be a polymer or a non-polymer. In addition, the above-mentioned polymer may be an oligomer (preferably an oligomer having a molecular weight of about 5000 or less, more preferably an oligomer having a molecular weight of about 1000 or less, such as an oligomer of about dimer to about pentamer) containing a monomer containing multiple aromatic rings as a monomer unit. The above-mentioned oligomer may be, for example, a homopolymer of a monomer containing multiple aromatic rings; a copolymer of two or more monomers containing multiple aromatic rings; a copolymer of one or more monomers containing multiple aromatic rings and other monomers; etc. The above-mentioned other monomers may be an aromatic ring-containing monomer that does not belong to the monomer containing multiple aromatic rings, or a monomer without an aromatic ring, or a combination thereof.
[0157] As non-limiting examples of compounds containing multiple aromatic rings, there can be cited: compounds having a structure in which two or more non-condensed aromatic rings are bonded via a linking group, compounds having a structure in which two or more non-condensed aromatic rings are directly (i.e., not via other atoms) chemically bonded, compounds having a condensed aromatic ring structure, compounds having a fluorene structure, compounds having a dinaphthothiophene structure, compounds having a dibenzothiophene structure, etc. The compounds containing multiple aromatic rings can be used alone or in combination of two or more.
[0158] As an additive (H RO) can be listed as follows: a compound that can be used as a monomer (m3); an oligomer containing a compound that can be used as a monomer (m3) as a monomer unit; a compound having a structure in which a group having an ethylenically unsaturated group (which can be a substituent bonded to a ring-constituting atom) or a portion of the group that constitutes an ethylenically unsaturated group is removed from the compound that can be used as a monomer (m3) and replaced with a group not having an ethylenically unsaturated group (for example, a hydroxyl group, an amino group, a halogen atom, an alkyl group, an alkoxy group, an alkoxyalkyl group, an aryloxy group, an ester group (such as an acetoxyalkyl group), a hydroxyalkyl group, a hydroxyalkyloxy group, a glycidoxy group, etc.) or a hydrogen atom; and the like compounds having a symmetrical or asymmetrical structure, but are not limited to these substances.
[0159] The above-mentioned double bond-containing ring (typically an aromatic ring, preferably a carbon ring) may have one or more substituents on the atoms constituting the ring, or may have no substituents. In some embodiments, for example, a compound having a double bond-containing ring and having an asymmetric structure due to the above-mentioned substituents may be preferably used as an additive (H RO ).
[0160] In some embodiments, as an additive (H RO ), it is preferred to use a compound containing a fused ring having a substituent (a compound containing a substituted fused ring). By containing this compound, the refractive index of the adhesive can be efficiently improved. From the perspective of the ease of preparation of the adhesive composition (for example, solubility in the solvent used in the solvent-type adhesive composition) and compatibility in the adhesive, the above-mentioned compound may also be advantageous. Here, the so-called fused ring having a substituent refers to a fused ring having one or more substituents on the ring-constituting atoms of at least one ring contained in the fused ring. The above-mentioned fused ring preferably contains a ring belonging to at least one of a heterocycle and a ring containing a double bond. For example, it is preferred to use a compound containing a substituted fused ring that becomes an asymmetric structure through the above-mentioned substituent as an additive (H RO ).
[0161] The additive (H RO), as the substituent, there can be exemplified: alkyl, alkoxy, alkoxyalkyl, aryloxy, ester group (acetoxyalkyl, etc.), aryloxy, hydroxyl, halogen atoms (fluorine atoms, chlorine atoms, bromine atoms, etc.), ethylenically unsaturated groups, hydroxyalkyl, hydroxyalkyloxy, glycidoxy, etc., but are not limited to these groups. In the substituent containing carbon atoms, the number of carbon atoms contained in the substituent is preferably 1 to 4, more preferably 1 to 3, for example, it can be 1 or 2. In some embodiments, the above-mentioned double bond-containing ring can be an aromatic ring as follows: an aromatic ring having no substituent on the ring-constituting atoms, or having one or more substituents selected from the group consisting of alkyl, alkoxy, alkoxyalkyl, ester group, ethylenically unsaturated group (such as (meth) acryloyloxy), hydroxyl and hydroxyalkyl. Among them, as preferred substituents, there can be listed: alkyl, alkoxy and alkoxyalkyl, and the number of carbon atoms contained in these substituents is preferably 1 to 4, more preferably 1 to 3, for example, it can be 1 or 2.
[0162] As an additive (H RO Preferred examples of the compound containing a substituted fused ring include dinaphthothiophene compounds (substituted DNT) having at least one substituent. RO ) adhesive can satisfactorily take into account both high refractive index and flexibility. The substituent possessed by the substituted DNT can be, for example, one or more selected from the group consisting of alkyl, alkoxy, alkoxyalkyl, (meth)acryloyloxy, and vinyl. From the perspective of low elastic modulus, substituted DNT having one substituent is preferred. Specific examples of such substituted DNTs include substituted DNTs having saturated substituents, such as 6-methoxymethyl dinaphthothiophene (6MDNTM, refractive index: 1.759) and 6-ethyl dinaphthothiophene (6EDNT, refractive index: 1.764); and substituted DNTs having ethylenically unsaturated substituents, such as 6-acryloyloxymethyl dinaphthothiophene (6MDNTA, refractive index: 1.737), 6-methacryloyloxymethyl dinaphthothiophene (6MDNTMA, refractive index: 1.726), 5-acryloyloxyethyl dinaphthothiophene (5EDNTA, refractive index: 1.786), 6-acryloyloxyethyl dinaphthothiophene (6EDNTA, refractive index: 1.722), 6-vinyl dinaphthothiophene (6VDNT, refractive index: 1.802) and 5-vinyl dinaphthothiophene (abbreviation: 5VDNT, refractive index: 1.793).
[0163] In some embodiments, as an additive (H RO), a compound without ethylenically unsaturated groups can be preferably used. This can inhibit the deterioration of the adhesive composition caused by heat and light (for example, the reduction of coating properties caused by the progress of gelation and the increase of viscosity), the performance change of the adhesive (for example, the increase of elastic modulus and the reduction of elongation deformation caused by the reaction of ethylenically unsaturated groups), and improve the storage stability. RO ) in an adhesive sheet having an adhesive layer having an ethylenically unsaturated group, from the viewpoint of suppressing dimensional change, deformation (warping, undulation, etc.), generation of optical distortion, etc. caused by the reaction of the ethylenically unsaturated group, an additive (H RO ) is preferred.
[0164] When using additives (H RO ) in some embodiments, as the additive (H RO ), it is preferred to use a compound with an asymmetric structure. Here, a compound with an asymmetric structure refers to a compound having a molecular structure that does not belong to either linear symmetry or rotational symmetry. In addition, in the following, sometimes the additive (H RO ) is referred to as a "high refractive index additive (A)" or simply "additive (A)". By using the additive (A) in combination with a base polymer (e.g., an acrylic polymer), an adhesive that properly combines a high refractive index with flexibility can be satisfactorily realized. From the viewpoint of slowing down the increase in the elastic modulus of the adhesive even when the additive (A) is used in a relatively large amount relative to 100 parts by weight of the base polymer (e.g., an acrylic polymer), it is advantageous for the compound used as the additive (A) to have an asymmetric structure. Examples of the additive (A) include the additive (H) exemplified above. RO ) has an asymmetric structure. The additive (A) can be used alone or in combination of two or more.
[0165] In the technology disclosed herein, the additive (H RO The ratio of additive (A) to the total amount of additive (A / H RO ) is not particularly limited and can be selected from the range of 0 wt % to 100 wt %. RO ) can be, for example, 10 wt % or more, 25 wt % or more, or 40 wt % or more. In some embodiments, from the perspective of better exerting the effect of the additive (A), the above ratio (A / H) can be 10 wt % or more, 25 wt % or more, or 40 wt % or more. RO ) is appropriately 50 wt % or more, preferably 70 wt % or more, may be 85 wt % or more, may be 90 wt % or more, may be 95 wt % or more. In some preferred embodiments, as the additive (H RO), only one or more additives (A) may be used. That is, the above ratio (A / H RO ) may be 100 wt %.
[0166] Used as additive (H RO The refractive index n of the compound (which may be a compound of the additive (A)) a It is possible to make it possible to include the additive (H RO ) is selected in a manner that allows the desired refractive index to be obtained in the adhesive, and is not limited to a specific range. RO ) has a refractive index n a For example, it may be greater than 1.510, greater than 1.530, greater than 1.550, or greater than 1.570. In some embodiments, the additive (H RO ) has a refractive index n a It is suitable to be 1.600 or more, advantageously 1.620 or more, preferably 1.650 or more, more preferably 1.675 or more, and further preferably 1.700 or more. RO ), the freedom of choice of the base polymer that can constitute the adhesive with the target refractive index is expanded, for example, a base polymer with a lower refractive index can be selected. This can be advantageous from the perspective of achieving an adhesive that has a high refractive index and flexibility in a balanced manner. RO ) has a refractive index n a There is no particular upper limit, and from the viewpoint of the low temperature characteristics and transparency of the adhesive, for example, 3.000 or less is appropriate, and may be 2.500 or less, 2.000 or less, 1.900 or less, 1.850 or less, 1.825 or less, or 1.800 or less.
[0167] It should be noted that the additive (H RO ) (may be an additive (A).) a The measurement is performed using a prism coupler at a measurement wavelength of 594 nm and a measurement temperature of 25° C. As a prism coupler, a commercially available measuring device can be used, for example, a model "2010M" manufactured by Metricon or its equivalent. When a nominal value of the refractive index at 25° C. is provided by a manufacturer, the nominal value can be used.
[0168] Additives (H RO ) has a refractive index n a Preferably higher than the amount containing the additive (H RO ) The refractive index of the adhesive n T That is, it is preferred to contain the following formula: Δn A =na -n T The refractive index difference Δn is defined A Compounds greater than 0 as additives (H RO ) of the adhesive. In some embodiments, Δn A For example, it can be 0.010 or more, so as to effectively exert the effect of the additive (H RO ) from the viewpoint of the refractive index improvement effect brought about by the adhesive, it is advantageous to be 0.050 or more, preferably 0.100 or more, more preferably 0.125 or more, further preferably 0.150 or more, and may be 0.160 or more, 0.170 or more, 0.180 or more, or 0.190 or more. In addition, from the additive (H RO ) compatibility, transparency of the adhesive, etc., in some embodiments, Δn A For example, it may be less than 0.500, less than 0.400, or less than 0.300. RO ) has a refractive index n a and Δn A The above descriptions in this regard also apply to the additive (A).
[0169] Additives (H RO ) is not particularly limited, and may be, for example, 100 or more, 130 or more, or 150 or more. In some embodiments, the additive (H RO ) from the viewpoint of increasing the refractive index, the additive (H RO ) preferably has a molecular weight of 170 or more, more preferably 200 or more, 230 or more, 250 or more, 270 or more, or 300 or more. RO The molecular weight of the additive (H ) may be less than about 10,000 or less than 5,000. From the viewpoint of achieving a balanced effect of high refractive index and other properties (e.g., optical properties such as flexibility suitable for adhesives and haze), it is preferably less than 3,000, more preferably 1,000 or less or less than 1,000, and may be less than 800, may be 600 or less (e.g., less than 600), may be less than 500, or may be less than 400. From the viewpoint of easy preparation of the adhesive composition and improved compatibility within the adhesive, the additive (H ) may be less than 10,000 or less. RO ) may be advantageous if the molecular weight is not too large. In some embodiments, a compound having a molecular weight of about 200 to about 600 (e.g., greater than or equal to 300 and less than 500) may be preferably used as an additive (H RO ). With additives (H RO ) can also be applied to the additive (A).
[0170] As an additive (HRO The molecular weight of the additive (H) may be calculated based on the chemical structure or measured using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) for a non-polymer or a polymer with a low degree of polymerization (e.g., about a dimer to about a pentamer). RO ) is a polymer with a higher degree of polymerization, the weight average molecular weight (Mw) obtained based on GPC performed under appropriate conditions can be used. When a nominal value of molecular weight is provided by a manufacturer, the nominal value can be adopted.
[0171] In some embodiments of the technology disclosed herein, the additive (H RO ) is typically a compound that is not a gas at 25°C, preferably a liquid (liquid) or non-gas compound at 25°C. It should be noted that in this specification, "liquid" means fluidity, and the state of the substance is liquid. The compound includes a compound with a melting point greater than 25°C. This makes it easy to obtain an adhesive with a moderate cohesive force that can exert the desired adhesive properties and elongation deformation. The additive (H RO ) has a melting point of, for example, preferably 30°C or higher, more preferably 40°C or higher, further preferably 50°C or higher, and may be 60°C or higher, 70°C or higher, or 80°C or higher. RO ) has no particular upper limit on the melting point. In some embodiments, from the perspective of ease of preparation of the adhesive composition, transparency of the adhesive, etc., the additive (H RO ) may have a melting point of, for example, 350°C or less, 300°C or less, 250°C or less, or 200°C or less. RO ) can also be applied to the additive (A).
[0172] In some embodiments, from the viewpoint of ease of blending with an adhesive, etc., as an additive (H RO ) The compound used is preferably soluble in a solvent (typically an organic solvent). Being soluble here means showing solubility in at least one common solvent that can prepare a solution containing the compound in the common solvent at a concentration of at least 1.0 wt% (more preferably 2.0 wt% or more, further preferably 5.0 wt% or more, 10 wt% or more, 15 wt% or more, or 20 wt% or more) at 25°C. Examples of the above-mentioned common solvents include: acetic acid esters such as ethyl acetate or butyl acetate; lower ketones such as acetone or methyl ethyl ketone (MEK); aromatic hydrocarbon solvents such as benzene or toluene; mixed solvents thereof; etc. Among them, compounds showing the above-mentioned solubility in one or both of ethyl acetate and MEK are preferred. With the additive (H RO) can also be applied to the additive (A).
[0173] The additives (H RO The content of the additive (H) can be appropriately set to obtain an adhesive having desired properties. RO ) content refers to the use of multiple compounds as additives (H RO For example, when a compound belonging to the additive (A) and a compound not belonging to the additive (A) (i.e., a compound with an asymmetric structure and a compound with a symmetric structure) are used together as the additive (H RO ), their total content is referred to as additive (H RO ) content. Relative to 100 parts by weight of the base polymer, the additive (H RO ) content may be, for example, 5 parts by weight or more, 10 parts by weight or more, or 20 parts by weight or more. From the perspective of better exerting the effect of low elastic modulus and / or high refractive index, in some embodiments, the additive (H) may be 5 parts by weight or more, 10 parts by weight or more, or 20 parts by weight or more. RO ) content can be, for example, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, 45 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, or 65 parts by weight or more. In addition, relative to 100 parts by weight of the base polymer, the additive (H RO ) content can be, for example, 150 parts by weight or less. From the viewpoint of easily obtaining an adhesive having moderate cohesive force capable of exerting the desired adhesive properties and elongation deformability, in some embodiments, 120 parts by weight or less is appropriate, preferably 100 parts by weight or less, and can be 90 parts by weight or less, 80 parts by weight or less, 75 parts by weight or less, 70 parts by weight or less, 65 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, 50 parts by weight or less, or 45 parts by weight or less.
[0174] The content of the additive (A) in the adhesive disclosed herein can be appropriately set in a manner to obtain an adhesive having desired characteristics. Here, the content of the additive (A) refers to their total content when multiple compounds are used as additives (A). Relative to 100 parts by weight of the base polymer, the content of the additive (A) can be, for example, 5 parts by weight or more or more than 5 parts by weight, can be 10 parts by weight or more than 10 parts by weight, or can be 20 parts by weight or more than 20 parts by weight. From the perspective of better exerting the effect of low elastic modulus and / or high refractive index, in some ways, relative to 100 parts by weight of the base polymer, the content of the additive (A) can be, for example, 30 parts by weight or more or more than 30 parts by weight, from the perspective of better exerting the effect of low elastic modulus and / or high refractive index, preferably 35 parts by weight or more, more preferably 40 parts by weight or more, can be 45 parts by weight or more, can be 50 parts by weight or more, can be 60 parts by weight or more, can be 65 parts by weight or more. In addition, the content of the additive (A) can be, for example, 150 parts by weight or less relative to 100 parts by weight of the base polymer. From the perspective of easily obtaining an adhesive having a moderate cohesive force capable of exerting the desired adhesive properties and elongation deformation, in some embodiments, 120 parts by weight or less is appropriate, preferably 100 parts by weight or less, 90 parts by weight or less, 80 parts by weight or less, or 75 parts by weight or less. From the perspective of transparency and low-temperature properties of the adhesive, in some embodiments, the content of the additive (A) can be 70 parts by weight or less, 65 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, 50 parts by weight or less, or 45 parts by weight or less relative to 100 parts by weight of the base polymer.
[0175] (Crosslinking agent)
[0176] The adhesive composition used in the formation of the adhesive disclosed herein may contain a crosslinking agent as needed for the purpose of adjusting the cohesive force of the adhesive, etc. As the crosslinking agent, an isocyanate crosslinking agent, an epoxy crosslinking agent, an aziridine crosslinking agent, The crosslinking agents are well known in the field of adhesives, such as oxazoline crosslinking agents, melamine resins, and metal chelate crosslinking agents. Among them, isocyanate crosslinking agents and epoxy crosslinking agents can be preferably used. As other examples of crosslinking agents, monomers having two or more ethylenically unsaturated groups in one molecule, i.e., multifunctional monomers, can be cited. The crosslinking agents can be used alone or in combination of two or more.
[0177] As the isocyanate crosslinking agent, a bifunctional or higher isocyanate compound can be used, for example, aliphatic polyisocyanates such as trimethylene diisocyanate, butylene diisocyanate, pentamethylene diisocyanate (PDI), hexamethylene diisocyanate (HDI), dimer acid diisocyanate, etc.; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate (IPDI), 1,3-bis (isocyanatomethyl) cyclohexane, etc.; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate (XDI), etc.; allophanate bonds, biuret bonds, isocyanurate bonds, uretdione bonds, urea bonds, carbodiimide bonds, uretonimine bonds, etc. Modified polyisocyanates obtained by modifying the above isocyanate compounds with a diazinetrione bond or the like (e.g., isocyanurate form of HDI, allophanate form of HDI, etc.); polyol adducts of the above isocyanate compounds (e.g., trimethylolpropane adduct of XDI, etc.); etc. Examples of commercially available products include: trade names Takenate 300S, Takenate 500, Takenate 600, Takenate D110N, Takenate D120N, Takenate D140N, Takenate D160N, Takenate D165N, Takenate D178N, Takenate D178NL (all manufactured by Mitsui Chemicals), Sumidur T80, Sumidur L, Desmodur N3400 (all manufactured by Sumika Bayer Polyurethanes), Millionate MR, Millionate MT, Coronate L, Coronate HL, Coronate HX, Coronate 2770 (all manufactured by Tosoh Corporation), trade names Duranate A201H, Duranate TPA-100 (all manufactured by Asahi Kasei Corporation), etc. The isocyanate compound may be used alone or in combination of two or more. A difunctional isocyanate compound and a trifunctional or higher-functional isocyanate compound may be used in combination.
[0178] Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin type epoxy resins, ethylene glycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol glycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, diamine glycidyl amine, N,N,N',N'-tetraglycidyl meta-xylylenediamine, and 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, etc. These can be used alone or in combination of two or more.
[0179] Examples of the multifunctional monomer include ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, bisphenol A di(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, butanediol(meth)acrylate, hexanediol di(meth)acrylate, etc. The multifunctional monomer may be used alone or in combination of two or more.
[0180] In some embodiments, at least a portion of the crosslinking agent may use a bifunctional crosslinking agent having two crosslinking reactive groups (e.g., isocyanate groups) per molecule. By using a bifunctional crosslinking agent, a soft crosslinked structure is easily formed. A bifunctional crosslinking agent may be used alone or in combination of two or more. In addition, a bifunctional crosslinking agent may be used in combination with a trifunctional or higher crosslinking agent.
[0181] In some embodiments, as a crosslinking agent, a non-cyclic crosslinking agent (also referred to as a chain crosslinking agent) that does not have a ring structure such as an aromatic ring or an aliphatic ring can be preferably used. For example, among the above-mentioned isocyanate crosslinking agents, isocyanate compounds that do not have a ring structure such as an aromatic ring and an isocyanurate ring are preferably used. By using a non-cyclic isocyanate compound as a crosslinking agent, a crosslinking agent with high flexibility can be easily formed. As specific examples of the above-mentioned non-cyclic isocyanates, there can be cited: aliphatic isocyanate compounds (such as PDI, HDI), modified products of aliphatic isocyanate compounds (such as polyisocyanate modified products obtained by modifying the allophanate bond, biuret bond, urea bond, and carbodiimide bond of PDI and HDI). A non-cyclic crosslinking agent can be used alone or in combination of two or more. In some preferred embodiments, a non-cyclic bifunctional crosslinking agent can be used as a crosslinking agent.
[0182] In some ways, as a crosslinking agent, a crosslinking agent having a relatively long distance between a crosslinking reactive group (e.g., isocyanate group) and another crosslinking reactive group in one molecule can be used. Thus, a soft crosslinked structure having a length above the prescribed length is formed. For example, in a crosslinking agent, a compound having a number of atoms constituting a connecting chain connecting a crosslinking reactive group and other crosslinking reactive groups of more than 10 (e.g., more than 12 or more than 14) can be used as a crosslinking agent. The upper limit of the number of atoms constituting the above-mentioned connecting chain can be prepared by polymerization, etc. according to the purpose, so there is no particular restriction, for example, less than 2000, less than 1000, less than 500, less than 100, less than 50, less than 30, or less than 20. It should be noted that the number of atoms constituting the connecting chain connecting the above-mentioned crosslinking reactive groups refers to the minimum number of atoms required for reaching another crosslinking reactive group (in the case of having more than three crosslinking reactive groups, the crosslinking reactive group closest to the above-mentioned crosslinking reactive group) from one crosslinking reactive group in a crosslinking agent. The above-mentioned crosslinking agent with a connecting chain can be used alone or in combination of two or more. In some preferred embodiments, a non-cyclic bifunctional crosslinking agent can be used as the crosslinking agent. Examples of commercially available products of the crosslinking agent include Coronate 2770 (manufactured by Tosoh Corporation), Takenate D178NL (manufactured by Mitsui Chemicals), Duranate A201H (manufactured by Asahi Kasei Corporation), etc.
[0183] The amount used when using a crosslinking agent (which may be a multifunctional monomer) is not particularly limited, and for example, it may be in the range of about 0.001 to about 5.0 parts by weight relative to 100 parts by weight of the above-mentioned monomer components. From the viewpoint of improving the adhesion to the adherend, in some embodiments, the amount of the crosslinking agent used is preferably 3.0 parts by weight or less, more preferably 2.0 parts by weight or less, and may be 1.0 parts by weight or less, 0.5 parts by weight or less, or 0.2 parts by weight or less, relative to 100 parts by weight of the monomer components. In addition, from the viewpoint of appropriately exerting the effect of the use of the crosslinking agent, in some embodiments, the amount of the crosslinking agent used may be, for example, 0.005 parts by weight or more, 0.01 parts by weight or more, 0.05 parts by weight or more, 0.08 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, or 0.4 parts by weight or more, relative to 100 parts by weight of the monomer components.
[0184] In order to carry out the cross-linking reaction more effectively, a cross-linking catalyst can be used. Examples of cross-linking catalysts include metal cross-linking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, tetraacetylacetonate zirconium, ferric acetylacetonate, butyl tin oxide, and dioctyltin dilaurate. Among them, tin cross-linking catalysts such as dioctyltin dilaurate are preferred. The amount of the cross-linking catalyst used is not particularly limited. Considering the balance between the speed of the cross-linking reaction and the length of the service life of the adhesive composition, the amount of the cross-linking catalyst used can be, for example, in the range of about 0.0001 parts by weight or more and 1 part by weight or less, preferably in the range of 0.001 parts by weight or more and 0.5 parts by weight or less, relative to 100 parts by weight of the monomer component.
[0185] In the adhesive composition, a compound that can undergo keto-enol tautomerism can be contained as a crosslinking delay agent. Thus, the effect of extending the service life of the adhesive composition can be achieved. For example, in an adhesive composition containing an isocyanate crosslinking agent, a compound that can undergo keto-enol tautomerism can be preferably used. As a compound that can undergo keto-enol tautomerism, various β-dicarbonyl compounds can be used. For example, β-diketones (acetylacetone, 2,4-hexanedione, etc.) and acetoacetic esters (methyl acetoacetate, ethyl acetoacetate, etc.) can be preferably used. The compound that can undergo keto-enol tautomerism can be used alone or in combination of two or more. Relative to 100 parts by weight of the monomer component, the amount of the compound that can undergo keto-enol tautomerism can be, for example, 0.1 parts by weight or more and 20 parts by weight or less, 0.5 parts by weight or more and 10 parts by weight or less, or 1 part by weight or more and 5 parts by weight or less.
[0186] (Thickener)
[0187] In the adhesive disclosed herein, a tackifier may be contained. As a tackifier, known tackifier resins such as rosin tackifier resins, terpene tackifier resins, phenol tackifier resins, hydrocarbon tackifier resins, ketone tackifier resins, polyamide tackifier resins, epoxy tackifier resins, and elastomer tackifier resins may be used. These resins may be used alone or in combination of two or more. The amount of tackifier resin used is not particularly limited and may be set according to purpose and use to exert appropriate adhesive properties. In some embodiments, from the viewpoint of refractive index and transparency, it is appropriate that the amount of tackifier used is less than 30 parts by weight relative to 100 parts by weight of monomer components, preferably less than 10 parts by weight, and more preferably less than 5 parts by weight. The technology disclosed herein may preferably be implemented without using a tackifier.
[0188] (High refractive index particles)
[0189] The adhesive disclosed herein may contain high refractive index particles as an optional component. Here, high refractive index particles refer to particles that can increase the refractive index of the adhesive by being included in the adhesive. Hereinafter, high refractive index particles are sometimes referred to as "particles P HRI "HRI refers to high refractive index.
[0190] As particle P HRI For example, one or more particles made of a material having a refractive index of 1.60 or more, preferably 1.70 or more (may be 1.80 or more, 1.90 or more, or 2.00 or more) can be used. HRI The upper limit of the refractive index of the material is not particularly limited, and may be, for example, 3.00 or less, 2.80 or less, 2.50 or less, 2.20 or less, or 2.00 or less. HRI The refractive index of a material is the refractive index obtained by measuring a single-layer film (thickness of the film that can measure the refractive index) of the material using a commercially available spectroscopic ellipsometer at a measuring wavelength of 589 nm and a measuring temperature of 25° C. As a spectroscopic ellipsometer, for example, a product name “EC-400” (manufactured by JA.Woolam Co., Ltd.) or an equivalent thereof can be used.
[0191] Particle P HRI The type of the adhesive is not particularly limited, and one or more materials capable of increasing the refractive index of the adhesive can be selected from metal particles, metal compound particles, organic particles, and organic-inorganic composite particles. HRI Inorganic oxides (such as metal oxides) that can increase the refractive index of the adhesive sheet can be preferably used. HRI Preferred examples of materials include inorganic oxides (specifically metal oxides) such as titanium dioxide (titanium oxide, TiO2), zirconium dioxide (zirconium oxide, ZrO2), aluminum oxide, zinc oxide, tin oxide, copper oxide, barium titanate, niobium oxide (Nb2O5, etc.). Particles containing these inorganic oxides (such as metal oxides) can be used alone or in combination of two or more. Among them, particles containing titanium dioxide and zirconium dioxide are preferred, and particles containing zirconium dioxide are particularly preferred. In addition, as metal particles, for example, iron-containing materials, zinc-containing materials, tungsten-containing materials, and platinum-containing materials can have a high refractive index. As organic particles, the refractive index of particles containing resins such as styrene resins, phenolic resins, polyester resins, and polycarbonate resins is relatively high. As organic-inorganic composite particles, composites of the above-mentioned inorganic materials and organic materials, materials obtained by coating inorganic particles with organic materials such as resins, etc. can be listed. As particles PHRI From the viewpoint of compatibility with the binder component, particles obtained by surface-treating the above-mentioned organic particles or inorganic particles with a surface treatment agent may be used.
[0192] Particle P HRI The average particle size of the particles is not particularly limited, and particles of an appropriate size that can achieve a desired increase in the refractive index by being contained in the binder can be used. HRI The average particle size of the particles may be, for example, about 1 nm or more, and about 5 nm or more is appropriate. HRI The average particle size is preferably about 10nm or more, can be about 20nm or more, and can also be about 30nm or more. In addition, from the viewpoints of maintaining adhesive properties, it is appropriate that the upper limit of the above-mentioned average particle size is, for example, about 300nm or less, and from the viewpoint of improving the refractive index, it is preferably about 100nm or less, more preferably about 70nm or less, further preferably about 50nm or less, and can also be about 35nm or less (for example, about 25nm or less).
[0193] It should be noted that the above particles P HRI The average particle size refers to the volume average particle size, specifically, the particle size distribution measurement device based on the laser scattering / diffraction method for the particles P. HRI The particle size at which the cumulative value in the particle size distribution measured for the dispersion is 50% (50% volume average particle size; hereinafter, sometimes referred to as D 50 As a measuring device, for example, a product name "Microtrac MT3000II" manufactured by Microtrac Bell Co., Ltd. or an equivalent thereof can be used.
[0194] Particles P in the binder HRI The content of P is not particularly limited. HRI The content of may vary depending on the refractive index of the target adhesive sheet. HRI The content of can be appropriately set in consideration of the required adhesive properties, etc. so as to achieve a refractive index above a predetermined value. HRI The content of P may be, for example, about 75% by weight or less. From the viewpoint of adhesive properties and transparency, the particles P in the adhesive may be HRI The content of P may be about 50% by weight or less, or about 30% by weight or less. HRI The lower limit of the content of is not particularly limited, for example, it can be greater than 0% by weight, can be greater than 1% by weight, or can be greater than 5% by weight. HRIThe content of P is, for example, less than 10% by weight, less than 1% by weight, or less than 0.1% by weight. The technology disclosed herein can be used in a binder composition that does not substantially contain particles P. HRI way of implementation.
[0195] Particles P in the binder HRI The content of P can be determined based on the relative relationship with the amount of the base polymer contained in the adhesive. HRI The content of P may be, for example, about 100 parts by weight or less, and from the viewpoint of adhesive properties and transparency, may be about 60 parts by weight or less, or may be about 40 parts by weight or less. HRI The lower limit of the content of is not particularly limited, and can be, for example, greater than 0 parts by weight, 1 part by weight or more, or 5 parts by weight or more, relative to 100 parts by weight of the base polymer. HRI The content of is, for example, less than 30 parts by weight, less than 10 parts by weight, less than 1 part by weight, or less than 0.1 parts by weight.
[0196] (Other additives)
[0197] In addition, within the scope of not significantly hindering the effect of the present invention, as required, the adhesive disclosed herein or the adhesive composition for forming the adhesive may include plasticizers, softeners, colorants (dyes, pigments, etc.), fillers, antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, light stabilizers, preservatives, etc., which are known additives that can be used in adhesives. Regarding such various additives, conventionally known additives can be used, and the features of the present invention are not particularly given, so detailed description is omitted.
[0198] In some forms of adhesives, the content of compounds that are liquid at 25°C is limited. This is advantageous from the viewpoint of taking into account moderate cohesion, elongation and deformation properties, and high refractive index. For example, the content of compounds that are liquid at 25°C is appropriately less than 30 parts by weight, preferably less than 20 parts by weight or less than 10 parts by weight, preferably less than 5 parts by weight, and more preferably less than 3 parts by weight or less than 1 part by weight, relative to 100 parts by weight of the base polymer. An adhesive that does not substantially contain a compound that is liquid at 25°C may also be used.
[0199] <Adhesive Sheet>
[0200] According to this specification, a PSA sheet having a PSA layer is provided. The PSA constituting the PSA layer may be a PSA formed from any PSA composition disclosed herein (eg, a cured product of the PSA composition).
[0201] The above-mentioned adhesive sheet can be an adhesive sheet with a substrate having the form of the above-mentioned adhesive layer on one side or both sides of a non-peelable substrate (support substrate), or an adhesive sheet without a substrate (i.e., an adhesive sheet without a non-peelable substrate. Typically, an adhesive sheet consisting of an adhesive layer) in which the above-mentioned adhesive layer is held by a release liner. Objects such as adhesive tapes, adhesive labels, adhesive films, etc. can be included in the concept of the adhesive sheet mentioned here. The adhesive sheet disclosed here can be in a roll shape or in a monolithic shape. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.
[0202] The structure of a double-sided adhesive type substrate-free PSA sheet (substrate-free double-sided PSA sheet) is shown in Figure 1 , 2 middle. Figure 1 The illustrated pressure-sensitive adhesive sheet 1 has a structure in which both surfaces 21A, 21B of a pressure-sensitive adhesive layer 21 having no substrate are protected by release liners 31, 32, respectively, at least the pressure-sensitive adhesive layer side of which serves as a release surface. Figure 2 The adhesive sheet 2 shown has a structure in which one surface (adhesive surface) 21A of the adhesive layer 21 without substrate is protected by a release liner 31 with both sides being the release surface. When it is wound, the other surface (adhesive surface) 21B of the adhesive layer 21 contacts the back side of the release liner 31, thereby forming a structure in which the other side 21B is also protected by the release liner 31. From the viewpoint of being able to follow the flexibility of the adherend that is to be bent repeatedly, the technology disclosed herein is preferably implemented in the form of a substrate-free adhesive sheet consisting of an adhesive layer. For example, from the viewpoint of reducing the thickness of the adhesive sheet and improving the transparency of the adhesive sheet, the above-mentioned substrate-free adhesive sheet is preferred.
[0203] The adhesive sheet disclosed herein may have, for example, Figure 3 The cross-sectional structure is schematically shown in FIG. Figure 3The adhesive sheet 3 shown has a supporting substrate 10 and a first adhesive layer 21 and a second adhesive layer 22 supported by the first face 10A and the second face 10B of the supporting substrate 10, respectively. The first face 10A and the second face 10B are both non-peeling surfaces (non-peeling surfaces). The adhesive sheet 3 is used by pasting the surface (first adhesive surface) 21A of the first adhesive layer 21 and the surface (second adhesive surface) 22A of the second adhesive layer 22 on the adherend, respectively. That is, the adhesive sheet 3 is formed in the form of a double-sided adhesive sheet (double-sided adhesive adhesive sheet). The adhesive sheet 3 before use has the following structure: the first adhesive surface 21A and the second adhesive surface 22A are respectively protected by the release liner 31, 32 of the surface (peeling surface) with peelability by at least the adhesive surface side. Alternatively, the following structure can also be adopted: the release liner 32 is omitted, and the release liner of the double-sided release surface is used as the release liner 31, and the second adhesive surface 22A is contacted with the back of the release liner 31 by winding the adhesive sheet 3, so that the second adhesive surface 22A is also protected by the release liner 31.
[0204] The technology disclosed herein can be preferably implemented in the form of the above-mentioned double-sided adhesive sheet without substrate or with substrate for the purpose of fixing and bonding components (such as optical components). Alternatively, although not specifically shown in the figure, the adhesive sheet disclosed herein can be in the form of a single-sided adhesive sheet with substrate having an adhesive layer on only one side of a non-peelable substrate (support substrate). Examples of the form of single-sided adhesive sheets include Figure 3 The illustrated configuration does not include either the first adhesive layer 21 or the second adhesive layer 22 .
[0205] (Adhesive layer)
[0206] The adhesive layer of the adhesive sheet disclosed herein can be formed by applying (e.g., coating) the adhesive composition on a suitable surface and then curing the composition. The coating of the adhesive composition can be implemented using conventional coating machines such as gravure roll coaters, reverse roll coaters, contact roll coaters, dip roll coaters, bar coaters, knife coaters, spray coaters, etc.
[0207] The thickness of the adhesive layer is not particularly limited, for example, it can be 3 μm or more. In some ways, the thickness of the adhesive layer is, for example, 5 μm or more, which is appropriate, can be 10 μm or more, can be 15 μm or more, can be 20 μm or more, can be 30 μm or more, can be 50 μm or more, can also be 70 μm or more or 85 μm or more. By increasing the thickness of the adhesive layer, there is a tendency for the adhesive force to increase. In addition, in some ways, the thickness of the adhesive layer can be, for example, 300 μm or less, can be 250 μm or less, can be 200 μm or less, can be 150 μm or less, or can be 120 μm or less. In some preferred ways, the thickness of the adhesive layer is 100 μm or less, more preferably 75 μm or less, further preferably 70 μm or less, can be 50 μm or less, or can be 30 μm or less. From the viewpoint of thinning of the adhesive sheet, it is advantageous that the thickness of the adhesive layer is not too large. In addition, a thin adhesive layer has a tendency to have excellent followability to the adherend. The technology disclosed herein can be implemented, for example, preferably in a manner where the thickness of the adhesive layer is in the range of 3 μm to 200 μm (more preferably 5 μm to 100 μm). It should be noted that in the case of an adhesive sheet having a first adhesive layer and a second adhesive layer on the first and second sides of a substrate, the thickness of the adhesive layer can be applied to at least the thickness of the first adhesive layer. The thickness of the second adhesive layer can be selected from the same range. In addition, in the case of an adhesive sheet without a substrate, the thickness of the adhesive sheet is consistent with the thickness of the adhesive layer.
[0208] (Haze value)
[0209] In some embodiments, the haze value (sometimes also referred to as "haze") of the adhesive layer constituting the adhesive sheet can be, for example, 5.0% or less, preferably 3.0% or less, more preferably 2.0% or less, further preferably 1.0% or less, 0.9% or less, 0.8% or less, 0.5% or less, or 0.3% or less. The adhesive sheet having such a high transparency adhesive layer can be preferably applied to applications requiring high light transmittance (e.g., optical applications) and applications requiring good visual recognition of the performance of the adherend through the adhesive sheet in a composition with or without a substrate. The lower limit of the haze value of the adhesive layer is not particularly limited, and from the viewpoint of improving transparency, the smaller the haze value, the more preferred. On the other hand, in some embodiments, considering the refractive index and bonding characteristics, the haze value can be, for example, 0.05% or more, or 0.10% or more. These haze values related to the PSA layer can be preferably applied to the haze value of the PSA sheet when the technology disclosed herein is implemented in the form of a substrate-less PSA sheet (typically a PSA sheet composed of a PSA layer).
[0210] Here, the "haze value" refers to the ratio of diffuse transmitted light to total transmitted light when the object to be measured is irradiated with visible light. It is also called turbidity. The haze value can be expressed by the following formula.
[0211] Th(%)=Td / Tt×100
[0212] In the above formula, Th is the haze value (%), Td is the scattered light transmittance, and Tt is the total light transmittance. The haze value can be determined by the method described in the embodiments described below. The haze value of the adhesive layer can be adjusted, for example, by selecting the composition, thickness, etc. of the adhesive layer.
[0213] In some ways, the haze value of the adhesive sheet can be, for example, less than 10.0%, preferably less than 5.0%, more preferably less than 3.0%, further preferably less than 2.0%, less than 1.7%, less than 1.5%, less than 1.2%, less than 1.0%, less than 0.8%. Such a high transparency adhesive sheet can be preferably used for applications requiring high light transmittance (such as optical applications) and applications requiring good visual recognition of the performance of the adherend across the adhesive sheet. The lower limit of the haze value of the adhesive sheet is not particularly limited. From the perspective of improving transparency, the smaller the haze value, the more preferred. On the other hand, in some ways, considering the refractive index and adhesive properties, the haze value can be, for example, more than 0.05%, more than 0.1%, and more than 0.3%. The haze value of the adhesive sheet can be measured by the same method as the determination of the haze value of the above-mentioned adhesive layer. The above-mentioned haze value of the adhesive sheet can be obtained by selecting the type of substrate and the thickness of the substrate in the composition of the above-mentioned adhesive layer, etc.
[0214] (Total light transmittance)
[0215] In some ways, the total light transmittance of the adhesive layer is preferably 85.0% or more (for example, 88.0% or more, 90.0% or more or greater than 90.0%). The adhesive sheet having such a high transparency adhesive layer can be preferably applied to applications requiring high light transmittance (for example, optical applications) and applications requiring good visual recognition of the performance of the adherend through the adhesive sheet in a composition with a substrate or a composition without a substrate. The upper limit of the total light transmittance can be, for example, about 98% or less in practical terms, about 96% or less, or about 95% or less. In some ways, considering the refractive index and adhesive properties, the total light transmittance of the adhesive layer can be about 94% or less, about 93% or less, or about 92% or less. The total light transmittance is measured according to JIS K7136: 2000 using a commercially available transmittance meter. As a transmittance meter, the trade name "HAZEMETER HM-150" or its equivalent made by Murakami Color Technology Research Institute can be used. The total light transmittance can be measured by the method described in the examples described below. The total light transmittance of the pressure-sensitive adhesive layer can be adjusted by, for example, selecting the composition and thickness of the pressure-sensitive adhesive layer.
[0216] In some ways, the total light transmittance of the adhesive sheet is preferably 85.0% or more (for example, 88.0% or more, 90.0% or more or greater than 90.0%). Such a high transparency adhesive sheet can be preferably used for applications requiring high light transmittance (for example, optical applications) and applications requiring good visual recognition of the performance of the adherend through the adhesive sheet. The upper limit of the total light transmittance can be, for example, about 98% or less in practical terms, about 96% or less, or about 95% or less. In some ways, considering the refractive index and bonding properties, the total light transmittance of the adhesive sheet can be about 94% or less, about 93% or less, or about 92% or less. The total light transmittance of the adhesive sheet can be measured by the same method as the determination of the total light transmittance of the above-mentioned adhesive layer. The total light transmittance of the adhesive sheet can be obtained by the composition of the above-mentioned adhesive layer, the type of substrate, and the selection of the thickness of the substrate in the composition with the substrate.
[0217] (Peel Strength)
[0218] There is no particular restriction on the peel strength of the adhesive sheet to the glass plate. In some embodiments, the peel strength of the adhesive sheet to the glass plate (peel strength to the glass plate) is, for example, 0.1N / 25mm or more, and can be 0.5N / 25mm or more. In some preferred embodiments, the peel strength to the above-mentioned glass plate is 1.0N / 25mm or more, more preferably 1.5N / 25mm or more, further preferably 2.0N / 25mm or more, can be 3.0N / 25mm or more, can be 5.0N / 25mm or more, can be 6.0N / 25mm or more, 7.0N / 25mm or more, 8.0N / 25mm or more, 9.0N / 25mm or more, or 10N / 25mm or more. The adhesive sheet having a peel strength to the glass plate of more than the specified value is suitable for the joining and fixing of, for example, glass components. There is no particular restriction on the upper limit of the above-mentioned peel strength, for example, it can be 30N / 25mm or less, 25N / 25mm or less, or 20N / 25mm or less.
[0219] Here, the peel strength can be determined by the following operation: press-bonding on an alkali glass plate as an adherend, placing it under an environment of 23°C and 50% RH for 30 minutes, and then measuring the peel strength under the conditions of a peeling angle of 180 degrees and a pulling speed of 300 mm / min. During the measurement, as required, the adhesive sheet of the measurement object can be reinforced by affixing an appropriate backing material (e.g., a polyethylene terephthalate (PET) film having a thickness of about 25 μm to about 50 μm). More specifically, the peel strength can be measured according to the method described in the examples described later.
[0220] (Thickness of adhesive sheet)
[0221] The thickness of the adhesive sheet disclosed herein (adhesive sheet without substrate or adhesive sheet with substrate) can be, for example, 1000 μm or less, 350 μm or less, 200 μm or less, 120 μm or less, 75 μm or less, or 50 μm or less. In addition, from the perspective of operability, the thickness of the adhesive sheet can be, for example, 5 μm or more, 10 μm or more, 25 μm or more, 30 μm or more, 40 μm or more, 80 μm or more, or 130 μm or more.
[0222] It should be noted that the thickness of the adhesive sheet refers to the thickness of the portion that is attached to the adherend. Figure 3 In the PSA sheet 3 having the structure shown, the thickness is the thickness from the first PSA surface 21A to the second PSA surface 22A, and does not include the thickness of the release liners 31 and 32 .
[0223] <Supporting substrate>
[0224] Some forms of the PSA sheet may be in the form of a PSA sheet with a substrate having a PSA layer on one or both sides of a supporting substrate. The material of the supporting substrate is not particularly limited and can be appropriately selected according to the purpose and mode of use of the PSA sheet. As non-limiting examples of the substrate that can be used, there can be listed: polyolefin films with polyolefins such as polypropylene (PP) and ethylene-propylene copolymer as the main component, polyester films with polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN) as the main component, polyvinyl chloride films with polyvinyl chloride as the main component, and other plastic films; foam sheets formed by foams such as polyurethane foam, polyethylene (PE) foam, and polychloroprene foam; woven and non-woven fabrics obtained by using various fibrous materials (which can be natural fibers such as hemp and cotton; synthetic fibers such as polyester and vinylon; semi-synthetic fibers such as acetate, etc.) alone or in a blend; Japanese paper, high-quality paper, kraft paper, crepe paper, etc.; metal foils such as aluminum foil and copper foil; etc. The substrate can be a composite of these. Examples of such a composite substrate include a substrate having a structure in which a metal foil and the above-mentioned plastic film are laminated, and a plastic substrate reinforced with inorganic fibers such as glass cloth.
[0225] In some ways, various film substrates can be preferably used. The above-mentioned film substrate can be a porous substrate such as a foam film, a non-woven fabric sheet, can be a non-porous substrate, or can be a substrate of a structure obtained by laminating a porous layer and a non-porous layer. In some ways, as the above-mentioned film substrate, it is preferred to use a substrate comprising a resin film that can independently maintain a shape (self-supporting or non-dependent) as a base film. Here, "resin film" refers to a non-porous structure, typically a resin film that is substantially free of bubbles (non-porous). Therefore, the above-mentioned resin film is a concept that is different from a foam film and a non-woven fabric. As the above-mentioned resin film, it is preferred to use a film that can independently maintain a shape (self-supporting or non-dependent). The above-mentioned resin film can be a single-layer structure, or it can be a multilayer structure (such as a three-layer structure) of more than two layers.
[0226] As the resin material constituting the resin film, for example, the following can be used: polyester; polyolefin; polycycloolefin derived from a monomer having an aliphatic ring structure such as a norbornene structure; polyamide (PA) such as nylon 6, nylon 66, and partially aromatic polyamide; polyimide (PI) such as transparent polyimide (CPI); polyamideimide (PAI); polyetheretherketone (PEEK); polyethersulfone (PES); polyphenylene sulfide (PPS); polycarbonate (PC); polyurethane (PU); ethylene-vinyl acetate copolymer (EVA); fluororesins such as polytetrafluoroethylene (PTFE); acrylic resin; cellulose polymers such as triacetyl cellulose (TAC); polyarylate; polystyrene; polyvinyl chloride; polyvinylidene chloride; and other resins.
[0227] The above-mentioned resin film can be a film formed by a resin material containing a single such resin, or a film formed by a resin material obtained by blending two or more. The above-mentioned resin film can be unstretched or stretched (e.g., uniaxially stretched or biaxially stretched). For example, PET film, PBT film, PEN film, unstretched polypropylene (CPP) film, biaxially stretched polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, PP / PE blended film, cycloolefin polymer (COP) film, CPI film, TAC film, etc. can be preferably used. As an example of a preferred resin film from the viewpoint of strength and dimensional stability, PET film, PEN film, PPS film and PEEK film can be cited. From the viewpoints of easy availability, PET film and PPS film are particularly preferably used, wherein PET film is preferred.
[0228] In the resin film, within the range that does not significantly hinder the effect of the present invention, known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, and anti-blocking agents can be added as needed. The amount of the additives is not particularly limited and can be appropriately set according to the purpose of the adhesive sheet.
[0229] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.
[0230] The substrate may be substantially composed of such a base film. Alternatively, the substrate may further include an auxiliary layer in addition to the base film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printed layer for imparting a desired appearance to the substrate, a laminated layer, an antistatic layer, a primer layer, a peeling layer, and other surface treatment layers.
[0231] In some embodiments, as a supporting substrate, a substrate having light transmittance (hereinafter also referred to as a light transmittance substrate) can be preferably used. Thus, a light-transmitting adhesive sheet with a substrate can be formed. The total light transmittance of the light-transmitting substrate can be, for example, greater than 50%, or can be greater than 70%. In some preferred embodiments, the total light transmittance of the supporting substrate is greater than 80%, more preferably greater than 90%, or can be greater than 95% (for example, 95% to 100%). The above-mentioned total light transmittance is measured in accordance with JIS K 7136:2000 using a commercially available transmittance meter. As a transmittance meter, the trade name "HAZEMETER HM-150" manufactured by Murakami Color Technology Research Institute or its equivalent is used. As a preferred example of the above-mentioned light-transmitting substrate, a light-transmitting resin film can be listed. The above-mentioned light-transmitting substrate can be an optical film.
[0232] The thickness of the substrate is not particularly limited and can be selected according to the purpose of use and the mode of use of the adhesive sheet. The thickness of the substrate can be, for example, 500 μm or less. From the perspective of the operability and processability of the adhesive sheet, it is preferably 300 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 25 μm or less, or 10 μm or less. When the thickness of the substrate becomes smaller, there is a tendency to improve the followability of the surface shape of the adherend. In addition, from the perspectives of operability and processability, the thickness of the substrate can be, for example, 2 μm or more, 10 μm or more, or 25 μm or more.
[0233] For the surface of one side of the substrate to be laminated with the adhesive layer, corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, the formation of the primer layer using the coating of the primer (primer) and other previously known surface treatments can be implemented as needed. Such surface treatment can be a treatment for improving the anchoring property of the adhesive layer to the substrate. The composition of the primer used in the formation of the primer layer is not particularly limited and can be appropriately selected from the known composition. The thickness of the primer layer is not particularly limited, and it is usually appropriate to be about 0.01 μm to about 1 μm, preferably about 0.1 μm to about 1 μm. As other treatments that can be implemented to the substrate as needed, antistatic layer formation treatment, coloring layer formation treatment, printing treatment, etc. can be listed. These treatments can be applied alone or in combination.
[0234] <Adhesive Sheet with Release Liner>
[0235] The adhesive sheet disclosed herein can be in the form of an adhesive product obtained by contacting the surface (adhesive surface) of the adhesive layer with the release surface of the release liner. Therefore, according to this specification, a kind of adhesive sheet with release liner (adhesive product) is provided, which comprises: any adhesive sheet disclosed herein and a release liner having a release surface contacting with the adhesive surface of the adhesive sheet.
[0236] There are no particular restrictions on the release liner, and for example, a release liner having a release layer on the surface of a liner substrate such as a resin film, paper (which may be a paper laminated with a resin such as polyethylene) can be used; a release liner comprising a resin film formed of a low-adhesive material such as a fluorine-containing polymer (polytetrafluoroethylene, etc.), a polyolefin resin (polyethylene, polypropylene, etc.), etc. From the viewpoint of excellent surface smoothness, a release liner having a release layer on the surface of a resin film as a liner substrate, and a release liner comprising a resin film formed of a low-adhesive material can be preferably used. As a resin film, there are no particular restrictions as long as it is a film that can protect the adhesive layer, and for example, polyethylene (PE) film, polypropylene (PP) film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyester film (PET film, PBT film, etc.), polyurethane film, ethylene-vinyl acetate copolymer film, etc. can be cited. In forming the above-mentioned release layer, for example, known release agents such as polysiloxane release agents, long-chain alkyl release agents, olefin release agents, fluorine-containing release agents, fatty acid amide release agents, molybdenum sulfide, and silica powder can be used.
[0237] <Purpose>
[0238] There is no restriction on the use of the adhesive sheet disclosed herein, and it can be used for various purposes. The adhesive sheet disclosed herein can be used for various purposes requiring high refractive index and flexibility by virtue of having an adhesive that takes into account both high refractive index and flexibility. For example, in electronic devices such as portable electronic devices, it is suitable as a display device (image display device) such as a liquid crystal display device, an organic EL (electroluminescent) display device, a PDP (plasma display panel), and an electronic paper; devices (optical devices) such as input devices such as touch panels, and are particularly suitable as adhesive sheets for foldable displays and rollable displays. For example, in foldable displays and rollable displays, it is preferably used as a method of bonding or fixing, protecting, etc. of a member with a high refractive index. The adhesive sheet disclosed herein can have a softness that can withstand repeated bending operations while having a high refractive index, so it can follow the repeatedly bent adherend (foldable display, etc.) well in a state of being pasted on a foldable display or a rollable display. As the pasted object in this use mode, glass components such as window glass and protective glass used in foldable displays and rollable displays can be listed. In addition, the adhesive sheet disclosed herein is also easy to follow and adhere to the surface of a curved surface such as a three-dimensional shape of a portable electronic device, and is therefore also suitable for use in electronic devices with curved surfaces. In addition, in some preferred embodiments, the adhesive can be an adhesive with excellent heat resistance in addition to having a high refractive index and flexibility. The above-mentioned portable electronic devices are sometimes used in high temperature environments, and since their internal space carries heat due to the heating of electronic components, the advantage of using the above-mentioned heat-resistant adhesive sheet is great.
[0239] Examples of the portable electronic devices include: mobile phones, smart phones, tablet personal computers, notebook personal computers, various wearable devices (for example, wrist-worn devices such as watches, modular devices such as those worn on a part of the body with clips, straps, etc., eyewear devices such as glasses (monocular, binocular, and helmet-type), clothing devices such as accessories worn on shirts, socks, hats, etc., and ear-worn devices such as headphones), digital cameras, digital video cameras, audio devices (portable music players, voice recorders, etc.), calculators (desktop calculators, etc.), portable game devices, electronic dictionaries, electronic notepads, electronic books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. It should be noted that in this specification, "portable" is not sufficient to be merely portable, and it is essentially portable enough for an individual (a standard adult) to carry it relatively easily.
[0240] There are no particular restrictions on the material (adherend material) to which the adhesive sheet disclosed herein is to be attached, and examples thereof include: metal materials such as copper, silver, gold, iron, tin, palladium, aluminum, nickel, titanium, chromium, zinc, etc., or alloys containing two or more of them, such as polyimide resins, acrylic resins, polyether nitrile resins, polyether sulfone resins, polyester resins (PET resins, polyethylene naphthalate resins, etc.), polyvinyl chloride resins, polyphenylene sulfide resins, polyether ether ketone resins, polyamide resins (so-called aromatic polyamide resins, etc.), polyarylate resins, polycarbonate resins, cellulose polymers such as diacetyl cellulose and triacetyl cellulose, polyvinyl butyral polymers, various resin materials such as liquid crystal polymers (typically plastic materials), alumina, zirconia, alkali glass, alkali-free glass, quartz glass, carbon, etc. Inorganic materials, etc. The adhesive sheet disclosed herein can be used by attaching it to a member (such as an optical member) composed of the above materials.
[0241] The components and materials of the adhesive sheet disclosed herein for pasting objects (at least one adherend in the double-sided adhesive sheet) can include materials with a refractive index higher than that of conventional acrylic adhesives. The refractive index of the adherend material is, for example, above 1.50, wherein there are also adherend materials with a refractive index of above 1.55 or above 1.58, and there are also adherend materials with a refractive index of above 1.62 (for example, about 1.66). Such high refractive index adherend materials are typically resin materials. More specifically, polyester resins such as PET, polyimide resins, aromatic polyamide resins, polyphenylene sulfide resins, polycarbonate resins, etc. For such materials, the effect of using the adhesive sheet disclosed herein (suppressing the reflection of light caused by the refractive index difference) can be preferably exerted. The upper limit of the refractive index of the above-mentioned adherend material is, for example, below 1.80, and can be below 1.70. The adhesive sheet disclosed herein can be preferably used in a manner of pasting on an adherend (such as a component) with a high refractive index as described above. Preferred examples of such adherends include resin films having a refractive index of 1.50 to 1.80 (preferably 1.55 to 1.75, for example 1.60 to 1.70). The refractive index can be measured by the same method as the refractive index of the adhesive.
[0242] The components and materials (at least one adherend in a double-sided adhesive sheet) to which the adhesive sheet is pasted may be light-transmissive. Such an adherend can easily obtain the advantages of the effect (suppressing light reflection at the interface between the adherend and the adhesive sheet) brought about by the technology disclosed herein. The total light transmittance of the adherend is, for example, greater than 50%, and preferably may be greater than 70%. In some preferred embodiments, the total light transmittance of the adherend is greater than 80%, more preferably greater than 90%, and may be greater than 95% (for example, 95% to 100%). The adhesive sheet disclosed herein may preferably be used in a manner of pasting on an adherend (such as an optical component) having a total light transmittance greater than a specified value. The total light transmittance is measured using a commercially available transmittance meter according to JIS K 7136:2000. As a transmittance meter, the trade name "HAZEMETER HM-150" manufactured by Murakami Color Technology Research Institute or its equivalent can be used.
[0243] In some preferred embodiments, the adherend (e.g., a component) to which the adhesive sheet is pasted can be an adherend having the above-mentioned refractive index and the above-mentioned total light transmittance. Specifically, the adhesive sheet disclosed herein can be preferably pasted on an adherend, such as a component, having a refractive index of 1.50 or more (e.g., about 1.55 or more, about 1.58 or more, about 1.62 or more, about 1.66, etc.) and a total light transmittance greater than 50% (e.g., 70% or more, preferably 80% or more, more preferably 90% or more, and can also be 95% or more). In such a method of pasting on a component, the effect brought about by the technology disclosed herein can be particularly preferably exerted.
[0244] As an example of preferred use, optical use can be cited. More specifically, for example, as an optical adhesive sheet used for bonding optical components (optical component bonding), in the manufacture of products (optical products) using the above-mentioned optical components, etc., the adhesive sheet disclosed herein can be preferably used. The above-mentioned optical product can be a so-called non-polarizing plate. For example, in an optical product with a light source, it can be an optical product consisting only of a layer with a polarization degree of 80% or less from the visual recognition side of the light source (organic EL panel, etc.).
[0245] The above-mentioned optical component refers to a component having optical properties (such as polarization, light refraction, light scattering, light reflection, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.). As the above-mentioned optical component, as long as it is a component having optical properties, there is no particular restriction, for example, components constituting display devices (image display devices), input devices and other devices (optical devices) or components used in these devices can be listed, for example, polarizing plates, wave plates, phase difference plates, optical compensation films, brightness enhancement films, light guide plates, reflection films, anti-reflection films, hard coating (HC) films, impact absorption films, anti-fouling films, photochromic films, dimming films, transparent conductive films (ITO films), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates; components further stacked with these films (sometimes collectively referred to as "functional films"), etc. It should be noted that the above-mentioned "plate" and "film" each include plate-shaped, film-shaped, sheet-shaped, etc. For example, "polarizing film" includes "polarizing plate", "polarizing sheet", etc., and "light guide plate" includes "light guide film", "light guide sheet", etc. In addition, the above-mentioned "polarizing plate" includes a circular polarizing plate.
[0246] Examples of the display device include a liquid crystal display device, an organic EL display device, micro LED (μLED), mini LED (miniLED), PDP, electronic paper, etc. Examples of the input device include a touch panel, etc.
[0247] The optical component is not particularly limited, and examples thereof include components including glass, acrylic resin, polycarbonate, PET, metal thin film, etc. (e.g., sheet-shaped, film-shaped, or plate-shaped components). It should be noted that the "optical component" in this specification includes components that perform the functions of decoration and protection while maintaining the visual recognizability of the display device and input device (design film, decorative film, or surface protection film, etc.).
[0248] The technology disclosed herein can be preferably used, for example, to join optical films such as films having one or more functions of light transmission, reflection, diffusion, waveguide, light collection, diffraction, etc., and fluorescent films to other optical components (which may be other optical films). Among them, in joining optical films having at least one function of light waveguide, light collection, and diffraction, it is preferred that the entire joining layer has a high refractive index, which can be a preferred application object of the technology disclosed herein.
[0249] The adhesive disclosed herein can be preferably used for the bonding of optical films such as light-guiding films, diffusion films, fluorescent films, color-adjusting films, prisms, lens-shaped films, and microlens array films. In these uses, from the perspective of the miniaturization trend and high performance of optical components, it is required to improve thinning and light extraction efficiency. As an adhesive that can cope with this demand, the adhesive disclosed herein can be preferably used. In more detail, for example, in the bonding of light-guiding films and diffusion films, by adjusting the refractive index of the adhesive layer as a bonding layer (for example, high refractive index), it can help to thin. In the bonding of fluorescent films, by properly adjusting the refractive index difference between the fluorescent light-emitting body and the adhesive, the light extraction efficiency (which can also be understood as luminous efficiency) can be improved. In the bonding of color-adjusting films, by properly adjusting the refractive index of the adhesive in a manner that reduces the refractive index difference with the color-adjusting pigment, it can help to reduce the scattering component and improve the light transmittance. In the bonding of prisms, lens-shaped films, microlens array films, etc., by properly adjusting the refractive index of the adhesive, it can help to control the diffraction of light, improve brightness and / or viewing angle.
[0250] The adhesive sheet disclosed herein is preferably used in a manner of being pasted on an adherend with a high refractive index (which may be a layer, a component, etc. with a high refractive index), and can suppress the interface reflection with the above-mentioned adherend. As described above, the adhesive sheet used in this manner preferably has a small refractive index difference with the adherend and high adhesion at the interface with the adherend. In addition, from the viewpoint of improving the homogeneity of the appearance, the thickness uniformity of the adhesive layer is preferably high, for example, the surface smoothness of the adhesive surface is preferably high. In the case where the thickness of the adherend with a high refractive index is small (for example, in the case of less than 5 μm, less than 4 μm or less than 2 μm), it is particularly meaningful to suppress the reflection at the interface from the viewpoint of suppressing the coloring and color unevenness caused by the interference of the reflected light. As an example of such a use method, it can be cited: in a polarizing plate with a phase difference layer having a polarizer, a first phase difference layer and a second phase difference layer in sequence, a method for bonding the above-mentioned polarizer with the above-mentioned first phase difference layer and / or bonding the above-mentioned first phase difference layer with the above-mentioned second phase difference layer.
[0251] In addition, the adhesive sheet disclosed herein is suitable for high refractive index, so it can be preferably used in a manner pasted on the light-emitting layer (e.g., a high refractive light-emitting layer mainly composed of inorganic materials) of an optical semiconductor, etc. By reducing the refractive index difference between the light-emitting layer and the adhesive layer, it is possible to suppress reflection at their interface and improve light extraction efficiency. The adhesive sheet used in this way preferably has an adhesive layer with a high refractive index. From the viewpoint of improving brightness, the adhesive sheet is preferably low-colored. This is advantageous from the viewpoint of suppressing the unintentional coloring caused by the adhesive sheet.
[0252] It should be noted that, in this specification, a self-luminous element refers to a light-emitting element whose luminous brightness can be controlled by the value of the current flowing therethrough. A self-luminous element may be composed of a single body or an aggregate. Specific examples of self-luminous elements include light-emitting diodes (LEDs) and organic ELs, but are not limited to these elements. In addition, in this specification, a light-emitting device refers to a device that includes such a self-luminous element as a constituent element. Examples of the above-mentioned light-emitting devices include light source module devices (e.g., planar light-emitting body modules) used for lighting and display devices formed with pixels, but are not limited to these devices.
[0253] The adhesive disclosed herein can be used in microlenses and other lens components (for example, microlenses constituting microlens array films, lens components such as microlenses for cameras) used as components of cameras, light-emitting devices, etc., preferably as a coating layer covering the lens surface, a bonding layer of a component opposite to the above-mentioned lens surface (for example, a component having a surface shape corresponding to the lens surface), a filling layer filled between the above-mentioned lens surface and the above-mentioned component, etc. The adhesive disclosed herein is suitable for high refractive index, so even a lens with a high refractive index (for example, a lens composed of a high refractive index resin, a lens with a surface layer made of a high refractive index resin) can reduce the refractive index difference with the lens. This is advantageous from the perspective of thinning the above-mentioned lens and the product having the lens, and it also helps to suppress aberrations and increase the Abbe number. The adhesive disclosed herein, for example, can be used as a lens resin by itself in the form of being filled in a recess or gap of an appropriate transparent component.
[0254] There are no particular restrictions on the method of bonding optical components using the adhesive sheet disclosed herein, and for example, it may be (1) a method of bonding optical components to each other using the adhesive sheet disclosed herein, (2) a method of bonding optical components to components other than optical components using the adhesive sheet disclosed herein, or (3) a method in which the adhesive sheet disclosed herein is in a form including an optical component and the adhesive sheet is bonded to an optical component or a component other than an optical component. It should be noted that in the above-mentioned method (3), the adhesive sheet in a form including an optical component may be, for example, an adhesive sheet whose support is an optical component (e.g., an optical film). Such an adhesive sheet in a form including an optical component as a support may be understood as an adhesive-type optical component (e.g., an adhesive-type optical film). In addition, when the adhesive sheet disclosed herein is an adhesive sheet of a type having a support and the above-mentioned functional film is used as the above-mentioned support, the adhesive sheet disclosed herein may be understood as an "adhesive-type functional film" having an adhesive layer disclosed herein on at least one side of the functional film.
[0255] As described above, according to the technology disclosed herein, a laminate having an adhesive sheet disclosed herein and a member to which the adhesive sheet is attached is provided. The member to which the adhesive sheet is attached can be a member having the refractive index of the material of the adherend. In addition, the difference between the refractive index of the adhesive sheet and the refractive index of the member (refractive index difference) can be the refractive index difference between the adherend and the adhesive sheet. For the members constituting the laminate, as described as the above-mentioned members, materials, and adherends, repeated description is not repeated.
[0256] As understood from the above description and the following embodiments, matters disclosed by the present specification include the following matters.
[0257] [1] An adhesive having a refractive index of 1.50 or more and a storage modulus G'(25°C) [Pa] at 25°C and an elongation at break E of the adhesive B [%] Ratio (G'(25℃) / E B ) is greater than 1 and less than 50.
[0258] [2] The adhesive according to [1] above, wherein the elongation at break E B More than 500%.
[0259] [3] The adhesive according to [1] or [2], wherein the storage modulus G' (25°C) is 1.0×10 4 ~1.0×10 6 within the range.
[0260] [4] The adhesive according to any one of [1] to [3] above, wherein the adhesive has a glass transition temperature of 0° C. or less.
[0261] [5] A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer comprises the pressure-sensitive adhesive according to any one of [1] to [4] above.
[0262] [6] The pressure-sensitive adhesive sheet according to [5] above, wherein the pressure-sensitive adhesive layer has a thickness of 5 μm to 100 μm.
[0263] [7] The pressure-sensitive adhesive sheet according to [5] or [6] above, wherein the pressure-sensitive adhesive sheet has a haze of 3% or less.
[0264] [8] The adhesive sheet according to any one of [5] to [7] above, wherein the total light transmittance of the adhesive sheet is 85% or more.
[0265] [9] The adhesive sheet according to any one of [5] to [8] above, wherein the peel strength of the adhesive sheet to a glass plate is 0.1 N / 25 mm or more.
[0266]
[10] The adhesive according to any one of [1] to [4] above, wherein the adhesive comprises a base polymer and a high refractive index additive (H RO ).
[0267]
[11] The adhesive according to
[10] above, wherein the high refractive index additive (H RO ) is a compound with an asymmetric structure (ie, a high refractive index additive (A)).
[0268]
[12] The adhesive according to
[10] or
[11] above, wherein the high refractive index additive (H RO ) is 30 parts by weight or more.
[0269]
[13] The adhesive according to any one of
[10] to
[12] above, wherein the high refractive index additive (H RO ) is a compound having a ring containing a double bond.
[0270]
[14] The adhesive according to any one of
[10] to
[13] above, wherein the high refractive index additive (H RO ) is a compound having a heterocyclic ring.
[0271]
[15] The adhesive according to any one of
[10] to
[14] above, wherein the high refractive index additive (H RO ) is a compound containing a fused ring having a substituent.
[0272]
[16] The adhesive according to any one of
[10] to
[15] above, wherein the adhesive contains a substituted dinaphthothiophene compound as the high refractive index additive (H RO ).
[0273]
[17] The adhesive according to any one of
[10] to
[16] , wherein the adhesive contains a compound with a refractive index of 1.65 or more as the high refractive index additive (H RO ).
[0274]
[18] The adhesive according to any one of
[10] to
[17] above, wherein the high refractive index additive (H RO ) is a compound having a molecular weight of 100 or more and 1000 or less.
[0275]
[19] The adhesive according to any one of [1] to [4] and
[10] to
[18] above, wherein the content of the aromatic ring-containing monomer in the monomer components constituting the base polymer is greater than or equal to 0 wt % and less than 75 wt %.
[0276]
[20] A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer comprises the pressure-sensitive adhesive according to any one of [1] to [4] and
[10] to
[19] .
[0277] Example
[0278] Hereinafter, some embodiments of the present invention will be described, but it is not intended to limit the present invention to the contents shown in these specific examples. It should be noted that in the following description, unless otherwise specified, the "parts" and "%" representing the usage amount and content are weight references.
[0279] <Example 1>
[0280] (Preparation of polymer solution)
[0281] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a cooler, 74 parts of n-butyl acrylate (BA), 25 parts of m-phenoxybenzyl acrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LIGHTACRYLATE POB-A", refractive index: 1.566, hereinafter referred to as "POB-A") and 1 part of 4-hydroxybutyl acrylate (4HBA) as monomer components, 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator and 150 parts of ethyl acetate as a polymerization solvent were added, and nitrogen was introduced while slowly stirring, and the liquid temperature in the flask was maintained at about 60°C to carry out a polymerization reaction for 6 hours, thereby preparing a solution of polymer P1 (polymer concentration 40%). The Mw of polymer P1 is 1.5 million.
[0282] (Preparation of Adhesive Composition)
[0283] The solution of the polymer P1 (polymer concentration 40%) was diluted with ethyl acetate to a polymer concentration of 20%. To 500 parts of the solution (containing 100 parts of polymer P1), 42 parts of 6-methoxymethyl dinaphthothiophene (6MDNTM, refractive index: 1.759, 25% ethyl acetate solution can be prepared), 0.1 parts of trimethylolpropane / xylylene diisocyanate adduct (Mitsui Chemicals, trade name "Takenate D-110N", solid content concentration 75%) as a crosslinking agent, 2 parts of acetylacetone as a crosslinking delay agent, and 1 part of a 1% ethyl acetate solution of ferric acetylacetonate as a crosslinking catalyst (0.01 parts of non-volatile components) were added and stirred to prepare the adhesive composition of this example.
[0284] (Manufacturing of adhesive sheet)
[0285] The adhesive composition prepared above was applied to the polysiloxane-treated surface of a polyethylene terephthalate (PET) film R1 (thickness 50 μm) treated with polysiloxane on one side, and heated at 130°C for 2 minutes to form an adhesive layer with a thickness of 50 μm. Next, the polysiloxane-treated surface of a PET film R2 (thickness 25 μm) treated with polysiloxane on one side was attached to the surface of the adhesive layer. Thus, a substrate-free double-sided adhesive sheet consisting of the adhesive layer was obtained. Both sides of the adhesive sheet were protected by PET films (release liners) R1 and R2.
[0286] <Example 2>
[0287] The adhesive composition of this example was prepared in the same manner as in Example 1 except that the amount of 6MDNTM used was changed to 70 parts per 100 parts of polymer P1. The adhesive sheet of this example (a substrate-free double-sided adhesive sheet composed of an adhesive layer having a thickness of 50 μm) was prepared in the same manner as in Example 1 except that the adhesive composition was used.
[0288] <Example 3>
[0289] A solution of polymer P2 (polymer concentration 40%) was prepared in the same manner as in Example 1 except that the composition of the monomer components was changed to 74 parts of 2-ethylhexyl acrylate (2EHA), 25 parts of POB-A, and 1 part of 4HBA. The Mw of polymer P2 was 1,000,000.
[0290] The adhesive composition of this example was prepared in the same manner as the adhesive composition of Example 1, except that a solution of polymer P2 was used instead of a solution of polymer P1. The adhesive sheet of this example (a substrate-free double-sided adhesive sheet composed of an adhesive layer having a thickness of 50 μm) was prepared in the same manner as Example 1, except that this adhesive composition was used.
[0291] <Example 4>
[0292] The adhesive composition of this example was prepared in the same manner as in Example 3 except that the amount of 6MDNTM used was changed to 70 parts relative to 100 parts of polymer P2. The adhesive sheet of this example (a substrate-free double-sided adhesive sheet composed of an adhesive layer having a thickness of 50 μm) was prepared in the same manner as in Example 1 except that the adhesive composition was used.
[0293] <Example 5>
[0294] A solution of polymer P3 (polymer concentration 40%) was prepared in the same manner as in Example 1 except that the composition of the monomer components was changed to 54 parts of 2EHA, 25 parts of POB-A, 20 parts of methoxyethyl acrylate (MEA), and 1 part of 4HBA. The Mw of polymer P3 was 1,000,000.
[0295] The adhesive composition of this example was prepared in the same manner as the adhesive composition of Example 1, except that a solution of polymer P3 was used instead of a solution of polymer P1. The adhesive sheet of this example (a substrate-free double-sided adhesive sheet composed of an adhesive layer having a thickness of 50 μm) was prepared in the same manner as Example 1, except that the adhesive composition was used.
[0296] <Example 6>
[0297] A solution of polymer P4 (polymer concentration: 40%) was prepared in the same manner as in Example 1 except that the composition of the monomer components was changed to 99 parts of BA and 1 part of 4HBA. The Mw of polymer P4 was 1.5 million.
[0298] The adhesive composition of this example was prepared in the same manner as the adhesive composition of Example 2, except that a solution of polymer P4 was used instead of a solution of polymer P1. The adhesive sheet of this example (substrate-free double-sided adhesive sheet composed of an adhesive layer) was prepared in the same manner as Example 1, except that the coating amount was adjusted so as to form an adhesive layer with a thickness of 20 μm.
[0299] <Example 7>
[0300] The adhesive composition of this example was prepared in the same manner as in Example 6 except that the amount of 6MDNTM used was changed to 60 parts per 100 parts of polymer P4. The adhesive sheet of this example (substrate-free double-sided adhesive sheet composed of an adhesive layer with a thickness of 20 μm) was prepared in the same manner as in Example 6 except that the adhesive composition was used.
[0301] <Example 8~Example 10>
[0302] In Example 8, 6-acryloyloxymethyl dinaphthothiophene (6MDNTA, refractive index: 1.737) was used, in Example 9, 6-acryloyloxyethyl dinaphthothiophene (6EDNTA, refractive index: 1.722) was used, and in Example 10, 6-ethyl dinaphthothiophene (6EDNT, refractive index: 1.764) was used in place of 6MDNTM in the preparation of the adhesive composition in Example 6, at a ratio of 42 parts to 100 parts of polymer P4. Otherwise, the adhesive composition of each example was prepared in the same manner as in the preparation of the adhesive composition in Example 6. The adhesive sheet of each example (substrate-free double-sided adhesive sheet composed of an adhesive layer with a thickness of 50 μm) was prepared in the same manner as in Example 1, except that the obtained adhesive composition was used.
[0303] <Example 11>
[0304] The adhesive composition of this example was prepared in the same manner as in Example 8 except that 6MDNTA was not used. The adhesive sheet of this example (substrate-free double-sided adhesive sheet composed of an adhesive layer with a thickness of 50 μm) was prepared in the same manner as in Example 1 except that this adhesive composition was used.
[0305] <Example 12>
[0306] 42 parts of 2,12-diallyloxy dinaphthothiophene (2,12-DAODNT, refractive index: 1.729) were used to replace 6MDNTA in the preparation of the adhesive composition in Example 8 with respect to 100 parts of polymer P4. The adhesive composition of this example was prepared in the same manner as the preparation of the adhesive composition in Example 8. The adhesive sheet of this example (a substrate-free double-sided adhesive sheet composed of an adhesive layer with a thickness of 50 μm) was prepared in the same manner as Example 1 except that the obtained adhesive composition was used.
[0307] <Example 13>
[0308] A solution of polymer P5 (polymer concentration 40%) was prepared in the same manner as in Example 1 except that the composition of the monomer components was changed to 95 parts of POB-A and 5 parts of 4HMA. The Mw of polymer P5 was 500,000.
[0309] The solution of the above-mentioned polymer P5 (polymer concentration 40%) was diluted with ethyl acetate to a polymer concentration of 20%. 10 parts of 6 MDNTA, 10 parts of 1% ethyl acetate solution (0.1 part of non-volatile components) of isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name "CORONATE HX", trifunctional isocyanate compound) as a crosslinking agent, 2 parts of acetylacetone as a crosslinking delay agent, 1 part of 1% ethyl acetate solution of ferric acetylacetonate as a crosslinking catalyst (0.01 part of non-volatile components) were added to 500 parts of the solution (containing 100 parts of polymer P5), and stirred and mixed, thereby preparing the adhesive composition of this example. Using this adhesive composition, the coating amount was adjusted in a manner to form an adhesive layer of thickness 25 μm. In addition, the adhesive sheet of this example (a substrate-free double-sided adhesive sheet consisting of an adhesive layer) was prepared in the same manner as in Example 1.
[0310] The structures of the substituted DNTs used in Examples 1 to 10, 12, and 13 are shown in Table 1. Among them, 2,12-DAODNT is a compound with a linear symmetrical structure, and the others are compounds with an asymmetrical structure. The refractive index of these compounds is measured by the following method. That is, a 5% ethyl acetate solution or a 5% MEK solution of the compound to be measured is applied on a glass plate in such a way that the dry film thickness becomes 10 μm, and it is heated at 130°C for 5 minutes to dry it. For the compound to be measured formed into a film on the above-mentioned glass plate by such operation, the refractive index is measured using a prism coupler (manufactured by Metricon, model "2010M") under the conditions of a measuring temperature of 25°C and a measuring wavelength of 594nm.
[0311]
[0312] <Evaluation method>
[0313] (Refractive index of adhesive)
[0314] The refractive index of the pressure-sensitive adhesive layer (substrate-less double-sided pressure-sensitive adhesive sheet) of each example was measured at a measurement temperature of 25° C. and a measurement wavelength of 594 nm using a prism coupler (manufactured by Metricon, model “2010M”).
[0315] (Storage modulus G' and glass transition temperature)
[0316] The adhesive layers of each example were stacked to form a sample with a thickness of about 1.5 mm, and punched into a disc-shaped sample with a diameter of 7.9 mm as a measurement sample. The dynamic viscoelasticity measurement was performed under the following conditions using the "Advanced RheometricExpansion System (ARES)" manufactured by Rheometric Scientific. The storage modulus G' [Pa] of the adhesive at each temperature (-20°C, 25°C and 60°C) was calculated from the measurement results. In addition, the temperature corresponding to the peak temperature of the dielectric loss tangent tanδ (loss elastic modulus G" / storage modulus G') in the above-mentioned dynamic viscoelasticity measurement was calculated and used as the glass transition temperature (Tg) [°C] of the adhesive.
[0317] [Measurement conditions]
[0318] Deformation mode: Twist
[0319] Measuring frequency: 1Hz
[0320] Temperature range: -50℃~150℃
[0321] Heating rate: 5℃ / min
[0322] Shape: Parallel plate 7.9mmφ
[0323] (Elongation at break E B )
[0324] The adhesive layer (substrate-free double-sided adhesive sheet) of each example was cut into a size of 30 mm in length and X mm in width in a form sandwiched between PET films (release liners) R1 and R2. The width X mm was set according to the thickness of the adhesive layer so that the cross-sectional area of the adhesive layer in the cross section along the width direction was about 2 mm. 2 Next, one release liner was removed to expose one surface of the adhesive layer, and the adhesive layer was wound around the other release liner with its longitudinal direction as the axis, thereby preparing a cylindrical sample with a length of 30 mm. The upper and lower 10 mm portions of the sample were fixed with the chuck clamps of a tensile testing machine (manufactured by SHIMAZU, EZ-S500N), and stretched at 25°C with a length of 10 mm between the chucks and a stretching speed of 300 mm / min, thereby measuring the elongation at break E of the sample. B [%].
[0325] (Total transmittance and haze)
[0326] Using a test piece obtained by laminating the adhesive layer of each example on an alkali-free glass (thickness of 0.8 mm to 1.0 mm, total light transmittance of 92%, haze of 0.4%), the total light transmittance and haze of the test piece were measured using a haze meter ("HM-150" manufactured by Murakami Color Technology Research Institute) under a measurement environment of 23°C. The value obtained by subtracting the total light transmittance and haze of the above-mentioned alkali-free glass from the measured value is used as the total light transmittance [%] and haze [%] of the adhesive (layer). For the substrate-free adhesive sheet composed of the above-mentioned adhesive layer, the total light transmittance [%] and haze [%] of the adhesive layer are the total light transmittance [%] and haze [%] of the adhesive sheet.
[0327] (Peel strength to glass plate)
[0328] Under the measuring environment of 23°C and 50%RH, the release liner was peeled off from one side of the adhesive sheet, a PET film with a thickness of 50 μm was attached and backed, and then cut into a size of 25 mm in width and 100 mm in length, and used as a test piece. The release liner on the other side was peeled off from the test piece, and it was crimped onto the surface of an alkali glass plate (manufactured by Matsunami Glass Industry Co., Ltd., with a thickness of 1.35 mm and a blue plate edge polished product) as an adherend by reciprocating a 2 kg roller once. It was placed in this environment for 30 minutes, and then the peel strength (adhesive force) [N / 25mm] was measured using a universal tensile compression tester according to JIS Z 0237:2000 at a pulling speed of 300 mm / min and a peeling angle of 180 degrees. As a universal tensile compression tester, a "tensile compression tester, TG-1kN" manufactured by Minebea Co., Ltd. was used. It should be noted that, in the case of a single-sided PSA sheet with a substrate, a PET film backing is not essential.
[0329] Table 2 shows the summary of the adhesive in each example and the evaluation results.
[0330]
[0331] As shown in Table 2, the adhesives of Examples 1 to 10 achieved a high ratio (G'(25°C) / E) by virtue of their low elastic modulus at 25°C and high elongation deformability. B )≤50, which balances high refractive index and softness. The adhesive layer (substrate-free adhesive sheet) of these examples has high transparency and shows good adhesion to glass by pressing at room temperature. In contrast, the refractive index of the adhesive of Example 11 is low, and the ratio (G'(25℃) / E B) is high and the flexibility is insufficient. In addition, the adhesive of Example 12 is turbid and the refractive index cannot be measured. It should be noted that the solubility of each substituted DNT used as an additive in Examples 1 to 10 in ethyl acetate is 6EDNTA>6MDNTM>6MDNTA>6EDNT. The solubility of 2,12-DAODNT in ethyl acetate is equivalent to that of 6MDNTA.
[0332] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the claims. The technology described in the claims includes various modifications and changes made to the specific examples described above.
[0333] Description of symbols
[0334] 1, 2, 3 adhesive sheets
[0335] 10 Support substrate
[0336] 10A first side
[0337] 10B Side 2
[0338] 21 adhesive layer, first adhesive layer
[0339] 21A bonding surface, first bonding surface
[0340] 21B adhesive surface
[0341] 22 second adhesive layer
[0342] 22A Second bonding surface
[0343] 31, 32 Release liner
Claims
1. An adhesive, wherein: The refractive index of the adhesive is greater than 1.50, and Storage modulus G'(25°C) [Pa] and elongation at break E of the adhesive at 25°C B [%] Ratio (G'(25℃) / E B ) is greater than 1 and less than 50.
2. The adhesive according to claim 1, wherein The elongation at break E B More than 500%.
3. The adhesive according to claim 1 or 2, wherein The storage modulus G'(25℃) is 1.0×10 4 ~1.0×10 6 within the range.
4. The adhesive according to claim 1 or 2, wherein The adhesive has a glass transition temperature of 0° C. or less.
5. An adhesive sheet, wherein: The pressure-sensitive adhesive sheet includes a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer includes the pressure-sensitive adhesive according to claim 1 or 2.
6. The adhesive sheet according to claim 5, wherein The adhesive layer has a thickness of 5 μm or more and 100 μm or less.
7. The adhesive sheet according to claim 5, wherein The adhesive sheet has a haze of 3% or less.
8. The adhesive sheet according to claim 5, wherein The total light transmittance of the adhesive sheet is greater than 85%.
9. The adhesive sheet according to claim 5, wherein The adhesive sheet has a peel strength with respect to a glass plate of 0.1 N / 25 mm or more.
Citation Information
Patent Citations
Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device
JP2007051271A
Adhesive composition, adhesive and adhesive sheet
JP2014169382A
Adhesive composition, adhesive and adhesive sheet
JP2017128732A
Game machine
JP2022110775A